AB0208 Reduced Hand Function Indicates Higher Disease Activity In Patients With Rheumatoid And Psoriatic Arthritis - Coppers, Birte; Heinrich, Simon; Bayat, Sara; Tascilar, Koray; Kleyer, Arnd; Simon, David; Minopoulou, Ioanna; Corte, Giulia; Fagni, Filippo; Schönau, Verena; Bohr, Daniela; Leyendecker, Sigrid; et al. (Annals of the Rheumatic Diseases, 2024)
Background: Measuring disease activity in patients with inflammatory arthritis remains challenging and is mainly based on physician-dependent assessments, subjective measures and just one blood biomarker of inflammation with no indication of the subclinical or functional state of the patients [1, 2]. Patients with rheumatoid arthritis (RA) and psoriatic arthritis (PsA) present with impaired hand function compared to healthy controls [3, 4]. While hand function is well studied in RA patients [5], data is sparse for PsA patients. Objectives: To employ the association between clinical disease activity scores and objectively measured hand function impairment in RA and PsA patients. Methods: Three conventional hand function tests were performed by PsA (CASPAR criteria) and RA (ACR/EULAR 2010 criteria) patients (Internal Medicine 3 outpatient clinics Erlangen, Germany) and healthy controls (HC) (study: Ethics #357_20B, DRKS00032490). The clinically assessed disease activity scores (Disease Activity in Psoriatic Arthritis Score (DAPSA) [1], Disease Activity Score 28 (DAS28) [2]) and the best trial for each of the hand function tests were used for this analysis: the highest out of three trials for an isometric grip strength test (Dynamometer, Saehan, Korea, Figure 1 A), the highest out of two trials for a dynamic grip strength test (Martin Vigorimeter, Germany, Figure 1 B) and the fastest out of two trials for the fine motor skill Moberg Picking-Up Test (MPUT) (Figure 1 C) for each hand. Mixed-effect linear regression models adjusted for age were used to employ the associations between the clinical disease activity scores and hand function tests of the patients. Analyses were stratified by sex. Results: We included 76 PsA patients (37 male, 52.0±4.3 years; DAPSA: 10.2±7.1), 73 RA patients (24 male, 53.9±14.1 years; DAS28: 2.6±0.9), and 77 HC (37 male, 46.0±18.5 years) in this study. For RA patients one-unit increase of the DAS28 was significantly associated with reduced dynamic grip strength for both sexes (Table 1, p<0.05) but not with a reduced isometric grip strength. Performance time of the MPUT was on average 11% (male) and 7% (female) longer with one-unit increase in the DAS28 score, but was not statistically significant. In PsA patients, a one-unit increase in the DAPSA score was associated with worse hand function on all measurements, but these were significant only in male patients (all p<0.05, Table 1). The MPUT showed worse performance of 2% in males and 1% in females for each one-point increase of the DAPSA score. Conclusion: Increased disease activity is associated with reduced hand function in PsA and RA patients. The dynamic grip strength test (vigorimeter) seems to be more sensitive than the isometric grip strength test (dynamometer) to detect functional changes in relation to disease activity. For male PsA patients, the fine motor MPUT may be particularly suitable to reflect changes in disease activity. Longitudinal properties of these measurements, such as sensitivity to change, need to be further explored. An overall low disease activity in PsA and RA patients is a limitation of our stud

AB0929 THE IMPACT OF KINESIOPHOBIA ON GAIT KINEMATICS IN PATIENTS WITH SPONDYLOARTHROPATHIES - Schweiger, Isabella; Koschinsky, J.; Elie-Tino, Godonou; Tascilar, Koray; Coppers, Birte; Kleyer, Arnd; Morf, Harriet; Simon, David; Bayat, Sara; Bohr, Daniela; Valor, L.; Raimondo, Maria Gabriella; et al. (Annals of the Rheumatic Diseases, 2024)
Background: In light of much needed functional assessments to monitor disease activity and functional status in spondyloarthritis (SpA), gait analysis is gaining interest. While it is generally known that the functional status and gait kinematics are closely related, it is unclear how fear of movement (kinesiophobia) affects gait kinematics in SpA patients. Objectives: To assess the influence of kinesiophobia on gait kinematics in patients with SpA and how sex mediates this relationship. Methods: A standardized 2-minute walk with self-selected walking speed was performed with 104 patients (psoriatic arthritis (PsA, CASPAR criteria) and ankylosing spondylitis (axSpa, ASAS criteria) (Internal Medicine 3 outpatient clinics Erlangen, Germany) in the hospital hallway. Spatio-temporal gait parameters (number of analyzed steps, cadence, gait velocity, double stance length and duration, swing left and right, stance left and right, temporal and spatial gait cycle variability) were recorded using the inertial sensor system RehaGait® (Hasomed, Magdeburg, Germany) and sagittal joint angles were computed and analyzed via MATLAB [1] (of the whole gait cycle the maximal and minimal flexion angle of left and right hip, knee, ankle). Patient characteristics and clinical assessments were retrieved from the patients record on the day of the gait analysis. Additionally, patients were asked to fill out the tampa scale of kinesiophobia (TSK) and an anamnestic questionnaire. Multivariate multiple linear regression was used to investigate the relationship between TSK score and kinematic gait parameters; mediation analysis was computed with sex as the control variable (potential mediator). Results: Patients characteristics of the 104 participants in this study are summarized in Table 1. Kinesiophobia affected the mediator sex (0.039; CI (0.005, 0.074), p=0.026) and the effect of kinesiophobia on gait kinematics differs between sexes. When controlling for the TSK score, male subjects took fewer steps and had a longer stance length. This may be due to them being taller (female: 166.6 cm, male: 179.9 cm; p<0.001). When controlling for sex, kinesiophobia is significantly associated with gait velocity (Coef: -0.009, p=0.003), double stance length (Coef: -0.005, p=0.031), double stance duration (Coef: 0.004, p=0.007), cadence (Coef: -0.39, p=0.006), swing phase left (Coef: -0.089, p=0.006) and the minimal left knee angle (Coef: -0.002, p=0.046). Conclusion: Patients with higher fear of movement scores by TSK walked slower, had a lower cadence, took smaller steps and had an increased extension of the left knee. While previous studies [2, 3] reported a decreased range of motion in axSpa patients compared to healthy subjects our results suggest that this can not only result from disease status itself, but that gait kinematics are associated with fear of movement. This is important to consider when gait analysis is used to assess the effect of interventions on functional status in SpA patient

AB0930 Towards Objective Measurement Of Spinal Mobility In Axial Spondyloarthritis – Benchmarking An Inertial Measurement Unit System With An Optical Measurement System - Blazek, V.; Loy, N.; Jukic, Elke; Coppers, Birte; Fleischmann, Martha Elisa; Hübner, Julian; Iqbal, M.; Heinrich, Simon; Scheiterer, Eduard; Leyendecker, Sigrid; Greenfield, Julia; Labinski, H.; et al. (Annals of the Rheumatic Diseases, 2024)

Accuracy and usability of a diagnostic decision support system in the diagnosis of three representative rheumatic diseases: a randomized controlled trial among medical students - Knitza, Johannes; Tascilar, Koray; Gruber, Eva; Kaletta, Hannah; Hagen, Melanie; Liphardt, Anna-Maria; Schenker, Hannah; Krusche, Martin; Wacker, Jochen; Kleyer, Arnd; Simon, David; Vuillerme, Nicolas; et al. (Arthritis Research & Therapy, 2021)
Background: An increasing number of diagnostic decision support systems (DDSS) exist to support patients and physicians in establishing the correct diagnosis as early as possible. However, little evidence exists that supports the effectiveness of these DDSS. The objectives were to compare the diagnostic accuracy of medical students, with and without the use of a DDSS, and the diagnostic accuracy of the DDSS system itself, regarding the typical rheumatic diseases and to analyze the user experience. Methods: A total of 102 medical students were openly recruited from a university hospital and randomized (unblinded) to a control group (CG) and an intervention group (IG) that used a DDSS (Ada – Your Health Guide) to create an ordered diagnostic hypotheses list for three rheumatic case vignettes. Diagnostic accuracy, measured as the presence of the correct diagnosis first or at all on the hypothesis list, was the main outcome measure and evaluated for CG, IG, and DDSS. Results: The correct diagnosis was ranked first (or was present at all) in CG, IG, and DDSS in 37% (40%), 47% (55%), and 29% (43%) for the first case; 87% (94%), 84% (100%), and 51% (98%) in the second case; and 35% (59%), 20% (51%), and 4% (51%) in the third case, respectively. No significant benefit of using the DDDS could be observed. In a substantial number of situations, the mean probabilities reported by the DDSS for incorrect diagnoses were actually higher than for correct diagnoses, and students accepted false DDSS diagnostic suggestions. DDSS symptom entry greatly varied and was often incomplete or false. No significant correlation between the number of symptoms extracted and diagnostic accuracy was seen. It took on average 7 min longer to solve a case using the DDSS. In IG, 61% of students compared to 90% in CG stated that they could imagine using the DDSS in their future clinical work life. Conclusions: The diagnostic accuracy of medical students was superior to the DDSS, and its usage did not significantly improve students’ diagnostic accuracy. DDSS usage was time-consuming and may be misleading due to prompting wrong diagnoses and probabilities. Trial registration: DRKS.de, DRKS00024433. Retrospectively registered on February 5, 2021.
CRIS-Team Scopus Importer:2021-09-17
Keywords: Accuracy; Apps; Clinical decision support system; Diagnosis; eHealth

A life span perspective on competencies for a healthy, physically active lifestyle: Findings of a data pooling initiative with over 7000 individuals - Carl, Johannes; Blaschke, Simon; Sudeck, Gorden; Schmid, Julia; Eckert, Katharina; Geidl, Wolfgang; Jaunig, Johannes; Köppel, Maximilian; Wiskemann, Joachim; Liphardt, Anna-Maria; Pfeifer, Klaus (European journal of sport science, 2024)
Individuals are recommended to lead active lifestyles throughout the life course. The model of physical activity-related health competence (PAHCO) adopts a competence approach by integrating physical, cognitive, and motivational determinants for health-enhancing PA (movement competence, control competence, self-regulation competence). Drawing on a comprehensive dataset pooling, the goal of the present study was to model the idiosyncratic courses of 10 PAHCO indicators over the life span. We identified studies that empirically operationalized PAHCO, combining data of 7134 individuals (age range: 15–97 years; 61% female) from 18 different populations (prevention and rehabilitation sectors). We applied a stepwise multilevel analysis approach with disjunct sub-samples (n = 48) to examine linear and quadratic associations between age and PAHCO. Indicators of movement competence (i.e., manageability of endurance, strength, and balance demands; task-specific self-efficacy) congruently showed negative associations with age (0.054 ≤ (Formula presented.) ≤ 0.211). However, parameters of control competence remained stable across the life span (−0.066 ≤ β ≤ 0.028). The three indicators of self-regulation competence revealed an inconsistent relationship with age, though uncovering positive associations for self-control (β = 0.106) and emotional attitude toward PA (β = 0.088). The associations of some indicators varied significantly across sub-samples. The results suggest differential analyses for associations between PAHCO and age. While the physically determined PAHCO indicators (movement competence) probably decline across the life span, the ability to ensure regularity of PA (self-regulation competence) or align PAs with an individual's health (control competence) appear to remain constant or improve with increasing age. The findings reinforce a de-stigmatizing approach for PA promotion practices with considerable space for aligning activities with health also in the elderly.
CRIS-Team Scopus Importer:2024-05-03
Keywords: age; competence; exercise; health; physical activity

ANALYTICAL APPROACH FOR DETERMINING THE SUITABILITY OF NINE CADIDATE BLOOD MARKERS FOR INVESTIGATING THE RESPONSE OF ARTICULAR CARTILAGE TO AMBULATORY LOAD - Herger, S.; Vach, W.; Liphardt, Anna-Maria; Egloff, C.; Nueesch, C.; Muendermann, A. (OSTEOARTHRITIS AND CARTILAGE, 2020)
CRIS-Team WoS Importer:2020-05-29

A Radar-Based Concept for Simultaneous High-Resolution Imaging and Pixel-Wise Velocity Analysis for Tracking Human Motion - Bräunig, Johanna; Heinrich, Simon; Coppers, Birte; Kammel, Christoph; Wirth, Vanessa; Stamminger, Marc; Leyendecker, Sigrid; Liphardt, Anna-Maria; Ullmann, Ingrid; Vossiek, Martin (IEEE Journal of Microwaves, 2024)
The radar-based analysis of human motion is actively being researched due to its contact- and markerless nature and ability to measure motion directly via the Doppler effect. Especially in medical and biomechanical fields, precise movement analysis is crucial. However, existing radar-based studies typically exhibit low lateral resolution, focusing on velocity evaluations and the tracking of scattering centers resolvable in the range or Doppler domains. In this work, we present a novel concept that enables a pixel-wise velocity analysis of human motion in radar near-field imaging scenarios. For this, we utilize the well-established back-projection technique to reconstruct consecutive radar images and perform a subsequent pixel-wise phase comparison. To accurately capture pixel-specific velocities along the depth dimension, this is followed by corrections of near-field geometry distortions accounting for aperture properties and pixel positions. Our theoretical derivations are supported by comprehensive point target simulations. To assess the performance of the proposed approach, we conducted a proof-of-concept study. We tracked a hand surface's movement while performing a finger tapping motion and compared the fingertip position and velocity determined by the radar with the respective values obtained from an optical marker-based system. The results showed a velocity measurement accuracy of 8.1mms−1 and a tracking accuracy of 1.4mm , demonstrating the great potential of our approach. The high angular resolution of the velocity measurement enables the tracking of the entire illuminated body shell, extending the range of future applications of radar-based motion analysis.<br
Keywords: Radar tracking; Radar; Radar imaging; Radar antennas; MIMO radar; Velocity measurement; Target tracking; Doppler radar; Signal resolution; Scattering; Human motion tracking; near-field imaging; radar imaging; velocity measurement

ASSOCIATION BETWEEN MECHANOSENSITIVE BLOOD MARKERS AND PATIENT REPORTED OUTCOMES IN PATIENTS WITH KNEE OSTEOARTHRITIS - Muendermann, A.; Nueesch, C.; Chammartin, F.; Herger, S.; Pagenstert, G.; Liphardt, Anna-Maria; Egloff, C. (OSTEOARTHRITIS AND CARTILAGE, 2022)
CRIS-Team WoS Importer:2022-04-22

Author Correction: Relationship between different serum cartilage biomarkers in the acute response to running and jumping in healthy male individuals (Scientific Reports, (2022), 12, 1, (6434), 10.1038/s41598-022-10310-z) - Dreiner, Maren; Munk, Tobias; Zaucke, Frank; Liphardt, Anna-Maria; Niehoff, Anja (Scientific Reports, 2022)
The original version of this Article contained errors in the spelling of the authors Maren Dreiner, Tobias Munk, Frank Zaucke, Anna-Maria Liphardt & Anja Niehoff which were incorrectly given as Dreiner Maren, Munk Tobias, Zaucke Frank, Liphardt Anna-Maria & Niehoff Anja respectively. The original Article has been corrected.
CRIS-Team Scopus Importer:2024-12-16

Automated Bone Density Measurements using Deep Learning - Folle, Lukas; Meinderink, Timo; Simon, David; Liphardt, Anna-Maria; Thies, Mareike; Krönke, Gerhard; Schett, Georg; Kleyer, Arnd; Maier, Andreas (23, 2022)
Introduction Hand bone loss is characteristic of rheumatoid or psoriatic arthritis, which clinically manifests with pain, swelling, and stiffness of the affected joints. Typically, hand joints are affected already in the early stages of arthritis1. High-resolution peripheral quantitative computed tomography (HR-pQCT) allows to visualize structural changes in the bone in 3D and enables measurements derived from the scans of the patient’s hand such as the volume of a bone. For this, a segmentation of the scans is necessary, which is reader-dependent and time-consuming, especially in challenging cases2. This work aims to replace this manual expert segmentation with a neural network (figure 1). Materials and methods The segmentation network was trained using 541 HR-pQCT patient scans (RA, PsA, and OA patients with motion grades up to 3) as input and the corresponding expert segmentation of the second metacarpal bone as reference. To optimize the parameters of the network, the current prediction was compared with the expert segmentation using the Dice coefficient. Pre-processing steps included resizing, flipping of left hands, and intensity normalization. The architecture of the segmentation network is based on the 2D U-Net, which was pre-trained on ImageNet. The predictions were resized to the original resolution and converted to the scanner-specific data format as post-processing steps. The scanner then calculated the average bone-mineral density (D100) based on the scan and the corresponding network-generated segmentation. The scans were split into training, validation, and testing with ratios of 70%, 20%, and 10% respectively. Results and discussion The bone segmentation using the neural network on the test set reached a Dice coefficient of 97.2%. A quantitative comparison of the network prediction (blue) and the expert annotation (red) is presented in figure 2. The deviation of the expert annotation from the bone contour is likely due to the shift of the scan when exceeding the specified maximum number of slices of the scanner. Since the neural network operates on a slice level, such deviations are implicitly accounted for. The results of the vBMD analysis are summarized in figure 3. Significant Pearson correlation with 0.999 (p<.001) was achieved for the D100 on the test set. Still, a slight offset is present in the predictions, which might lead to underestimating the D100. However, this could be eliminated in a calibration step beforehand. Conclusion Neural networks can be used to generate accurate segmentations of the MCP2 head even with erosions present and can be integrated into the clinical workflow with a performance on par with expert annotators and save time through the automation of the annotation process. <
Keywords: deep learning; bone imaging; segmentation

Baricitinib Improves Bone Biomechanical Properties in Rheumatoid Arthritis (RA) - Results of a Prospective Interventional Study - Kemenes, Stephan; Hartmann, Fabian; Tascilar, Koray; Simon, David; Bayat, Sara; Krönke, Gerhard; Mendez, Larissa Valor; Schuster, Louis; Liphardt, Anna-Maria; Schett, Georg; Kleyer, Arnd (ARTHRITIS & RHEUMATOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-13

Biomechanical properties of bone are impaired in patients with ACPA-positive rheumatoid arthritis and associated with the occurrence of fractures - Stemmler, Fabian; Simon, David; Liphardt, Anna-Maria; Englbrecht, Matthias; Rech, Jürgen; Hueber, Axel; Engelke, Klaus; Schett, Georg; Kleyer, Arnd (Annals of the Rheumatic Diseases, 2018)
OBJECTIVES: Bone loss is a well-established consequence of rheumatoid arthritis (RA). To date, bone disease in RA is exclusively characterised by bone density measurements, while the functional properties of bone in RA are undefined. This study aimed to define the impact of RA on the functional properties of bone, such as failure load and stiffness. METHODS: Micro-finite element analysis (µFEA) was carried out to measure failure load and stiffness of bone based on high-resolution peripheral quantitative CT data from the distal radius of anti-citrullinated protein antibody (ACPA)-positive RA (RA+), ACPA-negative RA (RA-) and healthy controls (HC). In addition, total, trabecular and cortical bone densities as well as microstructural parameters of bone were recorded. Correlations and multivariate models were used to determine the role of demographic, disease-specific and structural data of bone strength as well as its relation to prevalent fractures. RESULTS: 276 individuals were analysed. Failure load and stiffness (both P<0.001) of bone were decreased in RA+, but not RA-, compared with HC. Lower bone strength affected both female and male patients with RA+, was related to longer disease duration and significantly (stiffness P=0.020; failure load P=0.012) associated with the occurrence of osteoporotic fractures. Impaired bone strength was correlated with altered bone density and microstructural parameters, which were all decreased in RA+. Multivariate models showed that ACPA status (P=0.007) and sex (P<0.001) were independently associated with reduced biomechanical properties of bone in RA. CONCLUSION: In summary, µFEA showed that bone strength is significantly decreased in RA+ and associated with fractures.
EVALuna2:34448

BIOMECHANICAL PROPERTIES OF RADIAL BONE ARE DIFFERENT BETWEEN AUTO-ANTIBODY POSITIVE AND NEGATIVE RHEUMATOID ARTHRITIS - Stemmler, F.; Simon, David; Liphardt, Anna-Maria; Englbrecht, Matthias; Rech, Jürgen; Hueber, Axel; Engelke, Klaus; Schett, Georg; Kleyer, Arnd (2018)
EVALuna2:34998

Blood-Based Biomarkers of Inflammation and Tissue Remodeling Can Discriminate Between Rheumatoid Arthritis, Psoriasis, and Psoriatic Arthritis and Are Associated with Hand Function - Port Linares, Helena; Coppers, Birte; Bayat, Sara; Elie-Tino, Godonou; Fagni, Filippo; Corte, Giulia; Bay-Jensen, Anne-Christine; Tascilar, Koray; Hueber, Axel; Schönau, Verena; Sticherling, Michael; Heinrich, Simon; et al. (poster, American College of Rheumatology Convergence, 2023)

Bone Mass, Bone Microstructure and Biomechanics in Patients with Hand Osteoarthritis - Simon, David; Tascilar, Koray; Unbehend, Sara; Bayat, Sara; Berlin, Andreas; Liphardt, Anna-Maria; Meinderink, Timo; Rech, Jürgen; Hueber, Axel; Schett, Georg; Kleyer, Arnd (Journal of Bone and Mineral Research, 2020)
The impact of primary hand osteoarthritis (HOA) on bone mass, microstructure, and biomechanics in the affected skeletal regions is largely unknown. HOA patients and healthy controls (HCs) underwent high-resolution peripheral quantitative computed tomography (HR-pQCT). We measured total, trabecular, and cortical volumetric bone mineral densities (vBMDs), microstructural attributes, and performed micro–finite element analysis for bone strength. Failure load and scaled multivariate outcome matrices from distal radius and second metacarpal (MCP2) head measurements were analyzed using multiple linear regression adjusting for age, sex, and functional status and reported as adjusted Z-score differences for total and direct effects. A total of 105 subjects were included (76 HC: 46 women, 30 men; 29 HOA: 23 women, six men). After adjustment, HOA was associated with significant changes in the multivariate outcome matrix from the MCP2 head (p <.001) (explained by an increase in cortical vBMD (Δz = 1.07, p =.02) and reduction in the trabecular vBMD (Δz = −0.07, p =.09). Distal radius analysis did not show an overall effect of HOA; however, there was a gender-study group interaction (p =.044) explained by reduced trabecular vBMD in males (Δz = −1.23, p =.02). HOA was associated with lower failure load (−514 N; 95%CI, −1018 to −9; p = 0.05) apparent in males after adjustment for functional status. HOA is associated with reduced trabecular and increased cortical vBMD in the MCP2 head and a reduction in radial trabecular vBMD and bone strength in males. Further investigations of gender-specific changes of bone architecture in HOA are warranted. © 2020 The Authors. Journal of Bone and Mineral Research published by American Society for Bone and Mineral Research.
CRIS-Team Scopus Importer:2020-06-09
Keywords: ANALYSIS/QUANTITATION OF BONE; BIOMECHANICS; BONE QCT/MICROCT; DISEASES AND DISORDERS OF/RELATED TO BONE; ORTHOPAEDICS; OSTEOARTHRITIS

Bone micro-architecture, estimated bone strength, and the muscle-bone interaction in elite athletes: an HR-pQCT study - Schipilow, J. D.; Macdonald, H. M.; Liphardt, Anna-Maria; Kan, M.; Boyd, S. K. (Bone, 2013)
Athletes participating in sports characterized by specific loading modalities have exhibited different levels of augmentation of bone properties; however, the extent to which these loading environments affect bone micro-architecture and estimated bone strength (i.e., bone quality) remains unclear. Furthermore, the relative role of impact loading versus loading due to muscle forces in determining bone properties is confounded. The objectives of this study were 1) to examine the role of impact loading on bone quality of the distal radius and distal tibia in elite athletes, as determined by high resolution peripheral quantitative computed tomography (HR-pQCT) and finite element analysis (FEA), and 2) to investigate the relationship between bone quality and muscle strength in elite athletes. Ninety-five females (n=59) and males (n=36) between the ages of 16-30 years participated in the study. Participants included alpine skiers (high-impact), soccer players (moderate impact), swimmers (low-impact), and non-athletic controls. All group comparisons were made after accounting for age, height, and body mass. As expected, minimal differences in HR-pQCT parameters across groups were observed at the non weight-bearing distal radius. At the weight-bearing distal tibia, female alpine skiers and soccer players had significantly higher bone density, cortical thickness, and failure load (i.e., bone strength (N) in compression estimated by FEA) than swimmers (p<0.05). Female alpine skiers also had lower trabecular separation than swimmers and controls. Male alpine skiers had 20% higher trabecular bone mineral density than swimmers, and male soccer players exhibited 22% higher trabecular number than swimmers at the distal tibia (p<0.05). Male alpine skiers and soccer players had 28-38% higher failure load at the distal tibia than swimmers. No differences in bone parameters were observed between swimmers and controls for either sex at either site. Both muscle strength and sporting activity were predictors of failure load at the distal tibia in the female cohort. Sporting activity, but not muscle strength, was a significant predictor of failure load in the male cohort at both the radius and tibia. This data suggests that impact loading in sporting activity is highly associated with bone quality. Longitudinal and interventional studies are required to further clarify the muscle-bone interaction.
EVALuna2:13507

Bone micro-architecture of elite alpine skiers is not reflected by bone mineral density - Liphardt, Anna-Maria; Schipilow, J. D.; Macdonald, H. M.; Kan, M.; Zieger, A.; Boyd, S. K. (Osteoporosis international, 2015)
Bone quality is affected by muscle forces and external forces. We investigated how micro-architecture is influenced in elite alpine skiers who have received high loading levels throughout their adolescent bone development. Bone strength was higher in skiers, likely due to external forces, but muscle forces may also be a significant contributor.Impact loading and muscle forces affect bone quality, but little is known about how they influence 3 dimensional aspects of bone structure. This study investigated bone quality in female and male elite alpine skiers using high-resolution peripheral quantitative computed tomography (HR-pQCT).HR-pQCT at the distal radius and tibia, whole-body lean mass, and muscle strength were assessed in 10 female (22.7 ± 3.9 years) and 12 male (25.5 ± 3.3 years) Canadian national alpine team athletes and compared to recreationally active female (N = 10, 23.8 ± 3.2 years) and male (N = 12; 23.7 ± 3.6 years) control subjects. HR-pQCT standard parameters and customized cortical and finite element (FE) analyses were performed and analyzed using one-way ANOVA and Pearson's correlation.Male and female skiers had stronger bones than controls at radius (38-49 %, p < 0.001) and tibia (24-28 %, p < 0.001). This result was not consistently reflected by total bone mineral density (BMD) because higher trabecular BMD occurred in parallel with lower cortical BMD, which was due to a redistribution of mineral leading to a shift of the endocortical margin toward a thicker cortex. The endocortical regional adaptation was likely responsible for the greater strength of the athletes' bones. Lean mass and muscle strength was 29 to 90 % greater (p < 0.001) in athletes compared to controls. Good associations between muscle strength and FE-estimated bone strength were found (r = 0.63 to 0.80; p < 0.001), although micro-architecture was more strongly associated with muscle outcomes in females than males.Higher bone strength in elite alpine skiers is achieved through micro-architectural adaptation that is not apparent by BMD measurements alone. The improved micro-architecture at radius and tibia suggests that muscle forces may play an important role in bone adaptation.
EVALuna2:13501

Bone quality in osteopenic postmenopausal women is not improved after 12 months of whole-body vibration training - Liphardt, Anna-Maria; Schipilow, J.; Hanley, D. A.; Boyd, S. K. (Osteoporosis international, 2015)
Whole-body vibration training may improve bone quality through structural adaptation. We tested if 12 months of training affects bone structure in osteopenic postmenopausal women by using advanced 3-dimensional high-resolution imaging techniques. We found that whole-body vibration training did not improve bone structure compared to inactive controls.Whole-body vibration training (WBVT) has been suggested as a preventive measure against bone loss. Contradicting results of previous studies may be confounded by insufficiently sensitive bone density measures to detect relevant bone changes. WBVT may improve bone quality through structural adaptations, without increasing bone mineral density (BMD). We hypothesized that 12 months of WBVT will improve or maintain bone microarchitecture and bone strength in osteopenic postmenopausal women.Twenty-two women received WBVT for 2-3 sessions/week and were compared with 20 controls. Bone outcomes were measured by high-resolution peripheral quantitative CT (HR-pQCT, XtremeCT, Scanco Medical) and finite element estimated bone strength. Balance and jump performance and maximum voluntary contraction (MVC) of knee flexor and extensor muscles were recorded. All measurements were taken at baseline, 4, 8, and 12 months and a reduced data set at 4 and 8 months follow-up and compared using a mixed model repeated measures ANOVA.Thirty-one women completed the study with 90 % compliance (WBVT: n = 17, control n = 14). Total BMD (p < 0.001), cortical area*(p = 0.004), cortical thickness (p = 0.011), and cortical porosity (p = 0.024) all significantly decreased over time in both groups; WBVT did not affect the response. All other bone outcomes were not affected by WBVT or time. No difference in measures of balance, jump height, and MVC due to WBVT were detected.In our cohort, WBVT did not lead to improved bone quality in postmenopausal osteopenic women after 12 months of training compared to controls, and there were no detected benefits related to balance and muscle strength outcomes.
EVALuna2:13502

CD19-targeting CAR T-cell therapy in patients with diffuse systemic sclerosis: a case series - Auth, Janina; Müller, Fabian; Völkl, Simon; Bayerl, Nadine; Distler, Jörg H.W.; Tur, Carlo; Raimondo, Maria Gabriella; Chenguiti Fakhouri, Sara; Atzinger, Armin; Coppers, Birte; Eckstein, Markus; Liphardt, Anna-Maria; et al. (The Lancet Rheumatology, 2024)
Background: CD19-targeting chimeric antigen receptor (CAR) T-cell therapy has shown remarkable outcomes in patients with systemic lupus erythematosus. The effects of CD19-targeting CAR T cells on organ manifestations in patients with systemic sclerosis have yet to be characterised. B cells have a central role in the pathogenesis of systemic sclerosis. We present a detailed analysis of the effects of CD19-targeting CAR T-cell therapy in patients with systemic sclerosis. Methods: Six patients with severe diffuse systemic sclerosis with an insufficient response to at least two treatments were consecutively recruited at the Department of Internal Medicine 3, University Hospital Erlangen (Erlangen, Germany) to receive CD19-targeting CAR T-cell treatment (1 × 106 CAR T cells per kg bodyweight). Events were predefined by progression of interstitial lung disease, onset of congestive heart failure, onset of renal failure, onset of arterial hypertension, or initiation of new immunosuppressive or antifibrotic therapy. Event-free time or treatment intensification after study entry was the primary outcome. Key secondary outcomes included changes in the modified Rodnan Skin Score (mRSS), imaging (a component of the assessment of lung fibrosis), laboratory assessments, patient-reported outcomes, and a modified version of the American College of Rheumatology Composite Response Index in Systemic Sclerosis (ACR-CRISS), assessed at baseline, 3 months, 6 months, 9 months, and 12 months. Findings: Between April 20, 2022, and Nov 8, 2023, six patients with severe diffuse systemic sclerosis (median age 42 years [IQR 36–53]; four men and two women; all White European) were recruited and received CD19-targeted CAR T-cell therapy. The median follow-up time was 487 days (IQR 342–585). No events occurred within the observational period. Probability of improvement in the ACR-CRISS score increased to a median of 100% (IQR 100–100) at 6 months. Median mRSS decreased by 31% (IQR 29–38), corresponding to a median of 8 points (IQR 7–13) within 100 days. The extent of disease on CT scan decreased by a median of 4% (IQR 3–4) due to reduction of ground-glass opacities while the reticular pattern remained stable. Forced vital capacity improved by a median of 195 mL (IQR 18–275) at the latest observational timepoint. Interpretation: We provide the first evidence that CD19-targeting CAR T-cell therapy might intercept with the progression of fibrotic organ manifestations in patients with systemic sclerosis. Funding: Deutsche Forschungsgemeinschaft, Deutsche Krebshilfe, ELAN-Foundation Erlangen, IZKF Erlangen, and Bundesministerium für Bildung und Forschung.
CRIS-Team Scopus Importer:2024-12-13

Changes in mechanical loading affect arthritis-induced bone loss in mice - Liphardt, Anna-Maria; Windahl, Sara H.; Sehic, Edina; Hannemann, Nicole; Gustafsson, Karin L.; Bozec, Aline; Schett, Georg; Engdahl, Cecilia (Bone, 2020)
Arthritis induces bone loss by inflammation-mediated disturbance of bone homeostasis. On the other hand, pain and impaired locomotion are highly prevalent in arthritis and result in reduced general physical activity and less pronounced mechanical loading. Bone is affected by mechanical loading, directly through impact with the ground during movement and indirectly through muscular activity. Mechanical loading in its physiological range is essential for maintaining bone mass, whereas disuse leads to bone loss. The aim of this study was to investigate the impact of mechanical loading on periarticular bone as well as inflammation during arthritis. Mechanical loading was either blocked by botulinum neurotoxin A (Botox) injections before induction of arthritis, or enhanced by cyclic compressive loading, three times per week during arthritis induction. Arthritis was verified and evaluated histologically. Trabecular and cortical bone mass were investigated using micro-computed tomography (μCT), subchondral osteoclastogenesis and bone turnover was assessed by standard methods. Inhibition of mechanical loading enhanced arthritis-induced bone loss while it did not affect inflammation. In contrast, enhanced mechanical loading mitigated arthritis-induced bone loss. Furthermore, the increase in bone resorption markers by arthritis was partly blocked by mechanical loading. In conclusion, enhanced arthritic bone loss after abrogation of mechanical loading suggests that muscle forces play an essential role in preventing arthritic bone loss. In accordance, mechanical loading of the arthritic joints inhibited bone loss, emphasizing that weight bearing activities may have the potential to counteract arthritis-mediated bone loss.
CRIS-Team Scopus Importer:2019-11-29
Keywords: Antigen-induced arthritis; Bone microarchitecture; Mechanical loading; Periarticular bone loss; Unloading

CHRONIC TENOSYNOVITIS IS ASSOCIATED WITH LOSS OF GRIP STRENGTH IN PATIENTS WITH PSORIASIS AND PSORIATIC ARTHRITIS (OP0069) - Bayat, Sara; Coppers, Birte; Kleyer, Arnd; Elie-Tino, Godonou; Valor, L.; Simon, David; Fagni, Filippo; Corte, Giulia; Schönau, Verena; Tascilar, Koray; Hueber, Axel; Sticherling, Michael; et al. (Annals of the Rheumatic Diseases, 2023)
Background Rheumatic diseases result in joint destruction and impaired physical function [1]. We recently showed, that hand function based on objective tests may serve as a biomarker representing subclinical inflammation in psoriasis (Pso) patients and thus could support the early detection of psoriatic arthritis (PsA) onset [2]. Hand function tests are relevant for objective assessment of musculoskeletal function in relation to disease activity in PsA [3], However, the relationship of hand function with the synovitis and tenosynovitis detected by ultrasound (US) in PsA and Pso patients has not been well studied. Objectives To investigate the association of synovitis and tenosynovitis detected by US in greyscale (GS) and power doppler (PD) activity with grip strength and fine motor skills in patients with PsA and Pso. Methods PsA and Pso patients were recruited from the Rheumatology Department at the University Hospital erlangen, for this cross-sectional study. After giving written informed consent, subject characteristics were recorded and study participants underwent bilateral US of the wrists, metacarpophalangeal (MCP) joints, and flexor tendons of all fingers. Each joint was examined by GS (0-3), PD (0-3) and finally a combined score (PDUS: PD + GS) was calculated (0-3) [4]. The flexor tendon was scanned in GS (0/1) and with PD [0-3]. US activity considered either a synovitis or tenosynovitis score ≥1. Activity in tender joint count (TJC) and swollen joint count (SJC) 68/66 was considered ≥1 tender or ≥1 swollen joint. Hand function was assessed by vigorimetric grip strength (lbf) and the fine motor skill MPUT (Moberg pick-up test). For the analysis, patients’ hands were either divided in dominant/non-dominant or patient reported affected/non-affected hand. A correlation matrix was applied to measure the linear relation between the pairs of synovitis and tenosynovitis scores, grip strength and MPUT for both hands, using the Spearman correlation method. Results 106 patients (40 PsA, 66 Pso) participated in this study. Subject characteristics and general outcomes are summarized in Table 1. While grip strength was higher in the dominant hand (p<0.001), MPUT times are comparable between the dominant vs. non-dominant hands (p=0.056) but was faster in the non-affected hand (p=0.008). Low to moderate positive correlations were observed between both, overall GS synovitis score (MCP 2-5 + wrist) (r=0.24, p<0.05), and PDUS (r=0.23, p<0.05) with MPUT. In US active patients, a high correlation between grip strength and GS tenosynovitis score in digit 2 (r=-0.566, p=0.028) was detected. When considering patients with US in addition to SJC/TJC activity, imaging modalities did not correlate with hand function. Conclusion These findings indicate that the synovitis detected by greyscale is related with fine motor skills and tenosynovitis in greyscale with grip strength. This suggests, that chronic tenosynovitis has a greater impact on hand function than the acute inflammatory phase. When considering patients with TJC68/SJC66 ≥1 this relation is not present, suggesting that clinically assessed joint count, unlike ultrasonography, does not correlate with hand function impairmen

Classification of rheumatoid arthritis from hand motion capture data using machine learning - Fleischmann, Sophie; Holzwarth Correa, Vivien; Coppers, Birte; Sadeghi, Misha; Richer, Robert; Kleyer, Arnd; Simon, David; Bräunig, Johanna; Vossiek, Martin; Schönau, Verena; Schett, Georg; Koelewijn, Anne; et al. (13. Kongress der Deutschen Gesellschaft für Biomechanik (DGfB), 2024)
Intro Classifying movement restrictions in patients with rheumatoid arthritis (RA) is challenging. Machine learning (ML) can identify patterns in the data that cannot be captured with statistical tools. Aim To test the feasibility of classifying RA patients and controls from hand motion capture data using automatic feature extraction (AFE) and ML and to evaluate if a larger feature set improves the performance. Methods 24 RA patients (ACR/EULAR 2010 criteria) and 23 controls performed tipping and flexion of the hand [1], which was captured by an optoelectronic measurement system at 100 Hz with 29 reflective markers placed on the hand dorsum. We extracted the 3D trajectories, expressed relative to the central wrist marker and normalized to the hand length, of 24 markers on one hand (excluding thumb markers). After linearly interpolating missing values we filtered the data using a 4th-order Butterworth filter at a 6 Hz cut-off frequency and extracted a minimal and extensive feature set from the hand trajectories using the AFE package tsfresh [2]. We compared 4 classifiers in combination with scaling and dimensionality reduction (Fig 1). For every combination of algorithms, we trained a model using a stratified 10-fold nested cross-validation (CV). Hyperparameters were found from an inner five-fold CV on the respective train set using grid search. We report the accuracy of the best model averaged over the 10 folds. Results The best accuracy was 68.2% for flexion and 62.7% for tipping (Fig 2). Using the extensive instead of the minimal feature set led to no major change in accuracy. Summary The classification performance based on AFE was below the anticipated level of accuracy (>70%), likely due to the small dataset with limited data quality. We currently evaluate the approach on a more consistent, larger dataset and include expert features in addition to AFE. References [1] Phutane et al., Sensors, 21(4), 1208, 2021 [2] Christ et al., Neurocomputing, 307, 72-77, 20

Comparison and Improvement of CyberGlove III calibration methods - Heinrich, Simon; Michaelis, Johannes; Reiher, Isabella; Coppers, Birte; Lohmayer, Markus; Fleischmann, Martha Elisa; Kleyer, Arnd; Schett, Georg; De Craemer, Ann-Sophie; Elewaut, Dirk; Leyendecker, Sigrid; Liphardt, Anna-Maria (IEEE Sensors, 2024)
We investigate the accuracy of different calibration methods for the CyberGlove III for objective hand function assessments. The accuracy is evaluated by means of root-mean-squared errors (RMSE) between ground truth and angles estimated by the glove. Additionally, we propose two improvements. The first increases standardization capabilities for the measurement of pure thumb carpometacarpal joint flexion. The second increases the accuracy by extending an existing calibration method to all thumb and distal interphalangeal (DIP) joints. The best calibration method is identified and compared to an across-subject calibration by means of RMSEs, highlighting the tradeoff between the number of necessary measurements and the accuracy. Our proposed improvements both reduce the measurement effort, while only the second improvement reduces the RMSEs substantially. The best calibration method yields RMSEs below 10° for most joints, while the across-subject calibration has RMSEs that are approximately 5°–10° higher. We conclude that the CyberGlove III is a suitable tool for objective monitoring of hand movement and function, and the across-subject calibration has the potential to track the range of motion or frequency of joint movements. With this work, we provide an overview for researchers to choose calibration methods suitable for their application depending on necessary accuracy and possible extent of calibration measurements. This work further highlights potential obstacles, when such a glove is used with patients.<br

Comparison of different approaches for the personalization of a kinematic hand model - Heinrich, Simon; Phutane, Uday; Penner, Johann; Coppers, Birte; Liphardt, Anna-Maria; Leyendecker, Sigrid (conference, World Biomechanics Congress 2022, 2022)

Competencies for health-enhancing physical activity are associated with body mass: results of an updated data pooling across 18 samples - Carl, Johannes; Zheng, Miaobing; Popp, Johanna; Eckert, Katharina; Geidl, Wolfgang; Blaschke, Simon; Schmid, Julia; Grüne, Eva; Oppermann, Leonard; Liphardt, Anna-Maria; Morf, Harriet; Weißenfels, Anja; et al. (Obesity, 2024)
Objective: Although previous studies have illuminated associations between body mass and physical activity (PA), there have been scant insights regarding the physical, cognitive, and motivational determinants of PA in relationship to body mass. This study aimed to model courses of competencies for health-enhancing PA across the spectrum of BMI. Methods: We used cross-sectional data of 3670 individuals (mean [SD]: BMI, 25.54 [5.71] kg/m2; age, 46.11 [14.96] years) from a large data pooling with 18 primary samples employing the PA-related health competence (PAHCO) instrument. ANCOVA determined differences in 10 PAHCO indicators by BMI categories (underweight, normal weight, overweight, and obesity). Covariate-adjusted multilevel models described the nonlinear courses of the PAHCO indicators across the BMI spectrum. Results: The levels of all 10 PAHCO indicators differed significantly among the BMI categories (F ≥ 14.8; p < 0.001). All competencies for health-enhancing PA could be best described by cubic functions having their maximum around normal weight while regressing with underweight and with increasing grades of obesity (0.02 ≤ (Formula presented.) ≤ 0.31). Conclusions: This study adds to associations between BMI and PA levels by specifying individuals' multidimensional requirements for health-enhancing PA. The present findings call for an integration of physical, motivational, and cognitive factors in practices of PA promotion and sustainable obesity treatment.
CRIS-Team Scopus Importer:2024-10-04

Corrigendum: Editorial: Rising stars in environmental, aviation and space physiology: 2022(Front. Physiol., (2023), 14, (1230752), 10.3389/fphys.2023.1230752) - Saveko, Alina; Washio, Takuro; Petersen, Lonnie G.; Custaud, Marc Antoine; Liphardt, Anna-Maria (Frontiers in Physiology, 2023)
In the published article there was an error in the Author list, whereby author “Anna-Maria Liphardt” was erroneously listed as the second author. The corrected Author list appears below. “Alina Saveko, Takuro Washio, Lonnie G. Petersen, Marc-Antoine Custaud and Anna-Maria Liphardt”. In the published article, there was an error in affiliation for Marc-Antoine Custaud. Instead of “University Angers, CRC, CHU Angers, Inser, CNRS, MITOVASC, SFR CAT, Angers, France”, it should be “CRC, CHU Angers, Inserm, CNRS, MITOVASC, SFR ICAT, University of Angers, Angers, France”. The authors apologize for this error and state that this does not change the scientific conclusions of the article in any way. The original article has been updated.
CRIS-Team Scopus Importer:2023-08-11
Keywords: countermeasures; deconditioning; gravitational physiology; integrative physiology; weightlessness

Corrigendum to “Internal vascular anatomy of the human lacrimal gland: A protocol based on cadaver dissection and three-dimensional micro-computed tomography” [Ann. Anat. 252 (2024) 152207] (Annals of Anatomy (2024) 252, (S0940960223001620), (10.1016/j.aanat.2023.152207)) - Singh, Swati; Chopra, Prakshi; Necker, Fabian; Scholz, Michael; Liphardt, Anna-Maria; Schuster, Louis; Paulsen, Friedrich; Bräuer, Lars (Annals of Anatomy-Anatomischer Anzeiger, 2024)
The authors regret in the article by Singh et al. in volume 252;152207, February 2024, of Annals of Anatomy, the following change should be made in the acknowledgement section: 1. The present work was performed in (partial) fulfillment of the requirements for obtaining the degree of Dr. med (SS).The additional information provided does not influence the conclusions of the study. The authors would like to apologize for any inconvenience caused.
CRIS-Team Scopus Importer:2024-05-31

CyberGlove for clinical use? - Michaelis, Johannes; Reiher, Isabella; Heinrich, Simon; Coppers, Birte; Schett, Georg; Kleyer, Arnd; Elewaut, Dirk; De Craemer, Marieke; Leyendecker, Sigrid; Liphardt, Anna-Maria (FAU-Networking Night Medizintechnik, 2021)

Deep Learning-Based Classification of Inflammatory Arthritis by Identification of Joint Shape Patterns—How Neural Networks Can Tell Us Where to “Deep Dive” Clinically - Folle, Lukas; Simon, David; Tascilar, Koray; Krönke, Gerhard; Liphardt, Anna-Maria; Maier, Andreas; Schett, Georg; Kleyer, Arnd (Frontiers in Medicine, 2022)
Keywords: artificial intelligence; arthritis; joint; bone; deep learning

Deep learning methods allow fully automated segmentation of metacarpal bones to quantify volumetric bone mineral density - Folle, Lukas; Meinderink, Timo; Simon, David; Liphardt, Anna-Maria; Krönke, Gerhard; Schett, Georg; Kleyer, Arnd; Maier, Andreas (Scientific Reports, 2021)
Arthritis patients develop hand bone loss, which leads to destruction and functional impairment of the affected joints. High resolution peripheral quantitative computed tomography (HR-pQCT) allows the quantification of volumetric bone mineral density (vBMD) and bone microstructure in vivo with an isotropic voxel size of 82 micrometres. However, image-processing to obtain bone characteristics is a time-consuming process as it requires semi-automatic segmentation of the bone. In this work, a fully automatic vBMD measurement pipeline for the metacarpal (MC) bone using deep learning methods is introduced. Based on a dataset of HR-pQCT volumes with MC measurements for 541 patients with arthritis, a segmentation network is trained. The best network achieves an intersection over union as high as 0.94 and a Dice similarity coefficient of 0.97 while taking only 33 s to process a whole patient yielding a speedup between 2.5 and 4.0 for the whole workflow. Strong correlation between the vBMD measurements of the expert and of the automatic pipeline are achieved for the average bone density with 0.999 (Pearson) and 0.996 (Spearman’s rank) with p < 0.001for all correlations. A qualitative assessment of the network predictions and the manual annotations yields a 65.9% probability that the expert favors the network predictions. Further, the steps to integrate the pipeline into the clinical workflow are shown. In order to make these workflow improvements available to others, we openly share the code of this work.
Keywords: Rheumatic diseases; segmentation; deep learning

Differential diagnosis of RA and PsA using neural networks on 3D bone shape of finger joints - Folle, Lukas; Liu, Chang; Simon, David; Meinderink, Timo; Liphardt, Anna-Maria; Krönke, Gerhard; Schett, Georg; Maier, Andreas; Kleyer, Arnd (Annals of the Rheumatic Diseases 2021, 2021)
Keywords: Deep Learning; Rheumatoid arthritis; psoriatic arthritis

Does Subjectively Perceived Loss Of Hand Function Sufficiently Represent Ultrasonography-Detected Synovitis And Tenosynovitis In Patients With Psoriasis And Psoriatic Arthritis? - Coppers, Birte; Bayat, Sara; Elie-Tino, Godonou; Valor-Mendez, Larissa; Fagni, Filippo; Corte, Giulia; Tascilar, Koray; Hueber, Axel; Schönau, Verena; Sticherling, Michael; Schett, Georg; Kleyer, Arnd; et al. (poster, European Alliance of Association for Rheumatology (EULAR) Congress, 2023)

Dose-response relationship between ambulatory load magnitude and load-induced changes in COMP in young healthy adults - Herger, S.; Vach, Werner; Liphardt, Anna-Maria; Egloff, C.; Nuesch, C.; Mundermann, Annegret (Osteoarthritis and Cartilage, 2019)
Objective: To determine the dose-response relationship between ambulatory load magnitude during a walking stress test and load-induced changes in serum concentration of cartilage oligomeric matrix protein (sCOMP) in healthy subjects. Design: sCOMP was assessed before and after a 30-min walking stress test performed on three test days by 24 healthy volunteers. In each walking stress test, one of three ambulatory loads was applied in a block randomized crossover design: normal body weight (BW) (100%BW = normal load); reduced BW (80%BW = reduced load); increased BW (120%BW = increased load). Knee kinematics and ground reaction force (GRF) were measured using an inertial sensor gait analysis system and a pressure plate embedded in the treadmill. Results: Load-induced increases in sCOMP rose with increasing ambulatory load magnitude. Mean sCOMP levels increased immediately after the walking stress test by 26.8 ± 12.8%, 28.0 ± 13.3% and 37.3 ± 18.3% for the reduced, normal or increased load condition, respectively. Lower extremity kinematics did not differ between conditions. Conclusions: The results of this study provide important evidence of a dose-response relationship between ambulatory load magnitude and load-induced changes in sCOMP. Our data suggests that in normal weight persons sCOMP levels are more sensitive to increased than to reduced load. The experimental framework presented here may form the basis for studying the relevance of the dose-response relationship between ambulatory load magnitude and load-induced changes in biomarkers involved in metabolism of healthy articular cartilage and after injury.
CRIS-Team Scopus Importer:2019-06-18
Keywords: Cartilage mechanosensitivity; COMP; Kinematics; Serum biomarker; Treadmill walking

Dose-response relationship of in vivo ambulatory load and mechanosensitive cartilage biomarkers-The role of age, tissue health and inflammation: A study protocol - Herger, Simon; Vach, Werner; Nüesch, Corina; Liphardt, Anna-Maria; Egloff, Christian; Mündermann, Annegret (PLoS ONE, 2022)
OBJECTIVE: To describe a study protocol for investigating the in vivo dose-response relationship between ambulatory load magnitude and mechanosensitive blood markers of articular cartilage, the influence of age, cartilage tissue health and presence of inflammation on this relationship, and its ability to predict changes in articular cartilage quality and morphology within 2 years. DESIGN: Prospective experimental multimodal (clinical, biomechanical, biological) data collection under walking stress and three different load conditions varied in a randomized crossover design. EXPERIMENTAL PROTOCOL: At baseline, equal numbers of healthy and anterior cruciate ligament injured participants aged 20-30 or 40-60 years will be assessed clinically and complete questionnaires regarding their knee health. Biomechanical parameters (joint kinetics, joint kinematics, and surface electromyography) will be recorded while performing different tasks including overground and treadmill walking, single leg balance and hopping tasks. Magnetic resonance images (MRI) of both of knees will be obtained. On separate stress test days, participants will perform a 30-minute walking stress with either reduced (80% body weight (BW)), normal (100%BW) or increased (120%BW) load. Serum blood samples will be taken immediately before, immediately after, 30, 120 and 210 minutes after the walking stress. Concentration of articular cartilage blood biomarkers will be assessed using enzyme linked immunosorbent assays. At 24-month follow-up, participants will be again assessed clinically, undergo an MRI, complete questionnaires, and have a blood sample taken. CONCLUSION: The study design provides a standardized set up that allows to better understand the influence of ambulatory load on articular cartilage biomarkers and thereby extend current knowledge on in vivo cartilage metabolism and mechanosensitivity. Further, this study will help to elucidate the prognostic value of the load-induced cartilage biomarker response for early articular cartilage degeneration. TRIAL REGISTRATION: The protocol was approved by the regional ethics committee and has been registered at clinicaltrials.gov (NCT04128566).
CRIS-Team Scopus Importer:2022-09-09

Effect of disease-modifying anti-rheumatic drugs on bone structure and strength in psoriatic arthritis patients - Simon, David; Kleyer, Arnd; Bayat, Sara; Tascilar, Koray; Kampylafka, Eleni; Meinderink, Timo; Schuster, Louis; Petrov, Ramona; Liphardt, Anna-Maria; Rech, Jürgen; Schett, Georg; Hueber, Axel (Arthritis Research & Therapy, 2019)
Objectives: To address whether the use of methotrexate (MTX) and biological disease-modifying anti-rheumatic drugs (bDMARDs) impacts bone structure and biomechanical properties in patients with psoriatic arthritis (PsA). Methods: This is a cross-sectional study in PsA patients receiving no DMARDs, MTX, or bDMARDs. Volumetric bone mineral densities (vBMDs), microstructural parameters, and biomechanical properties (stiffness/failure load) were determined by high-resolution peripheral quantitative CT and micro-finite element analysis in the respective groups. Bone parameters were compared between PsA patients with no DMARDs and those receiving any DMARDs, MTX, or bDMARDs, respectively. Results: One hundred sixty-five PsA patients were analyzed, 79 received no DMARDs, 86 received DMARDs, of them 52 bDMARDs (TNF, IL-17-or IL-12/23 inhibitors) and 34 MTX. Groups were balanced for age, sex, comorbidities, functional index, and bone-active therapy, while disease duration was longest in the bDMARD group (7.8 ± 7.4 years), followed by the MTX group (4.6 ± 7.4) and the no-DMARD group (2.9 ± 5.2). No difference in bone parameters was found between the no-DMARD group and the MTX group. In contrast, the bDMARD group revealed significantly higher total (p = 0.001) and trabecular vBMD (p = 0.005) as well as failure load (p = 0.012) and stiffness (p = 0.012). In regression models, age and bDMARDs influenced total vBMD, while age, sex, and bDMARDs influenced failure load and stiffness. Conclusion: Despite longer disease duration, bDMARD-treated PsA patients benefit from higher bone mass and better bone strength than PsA patients receiving MTX or no DMARDs. These data support the concept of better control of PsA-related bone disease by bDMARDs.
CRIS-Team Scopus Importer:2019-07-16
Keywords: Biological agents; Bone; Computed tomography; Disease-modifying anti-rheumatic drugs; Methotrexate; Psoriatic arthritis

Effect of older age and/or ACL injury on the dose–response relationship between ambulatory load magnitude and immediate load-induced change in serum cartilage oligomeric matrix protein - Herger, Simon; Nüesch, Corina; Liphardt, Anna-Maria; Egloff, Christian; Mündermann, Annegret (Journal of Sport and Health Science, 2025)
Purpose: This study aimed to assess the influence of older vs. younger age and previous anterior cruciate ligament (ACL) injury on resting serum cartilage oligomeric matrix protein (sCOMP(tpre)) concentration, on immediate load-induced sCOMP kinetics after a 30-min treadmill walking stress (∆_sCOMP(tpost)), and on the dose–response relationship between ambulatory load magnitude and ∆_sCOMP(tpost). Methods: A total of 85 participants were recruited in 4 groups (20–30 years: 24 healthy, 23 ACL-injured; 40–60 years: 23 healthy, 15 ACL-injured). Blood samples were collected immediately before and after a walking stress at 80%, 100%, or 120% bodyweight (BW) on 3 test days and analyzed for sCOMP concentration. Linear models were used to estimate the effect of age, knee status (unilateral ACL injury, 2–10 years prior), and sex on sCOMP(tpre), ∆_sCOMP(tpost), and the dose–response between ambulatory load magnitude and ∆_sCOMP(tpost). Results: We found that sCOMP(tpre) was 21% higher in older than younger participants (p < 0.001) but did not differ between ACL-injured and healthy participants (p = 0.632). Also, ∆_sCOMP(tpost) was 19% lower in older than younger participants (p = 0.030) and increased with body mass index (p < 0.001), sCOMP(tpre) (p = 0.008), and with 120%BW (p < 0.001), independent of age, ACL injury, or sex. Conclusion: Age but not prior ACL injury influences resting sCOMP and load-induced sCOMP. The dose–response relationship between ambulatory load magnitude and load-induced sCOMP changes is not affected by age, ACL injury, or sex. A better understanding of systemic sCOMP and the role of its mechanoresponse for the understanding of osteoarthritis pathophysiology and monitoring intervention efficacy may require knowledge of individual cartilage composition and tissue-level loading parameters.
CRIS-Team Scopus Importer:2025-01-31
Keywords: Aging; Cartilage blood biomarker; Knee injury; Mechanosensitivity; Risk for OA

Effects of vibration training on bone metabolism: results from a short-term bed rest study - Baecker, Natalie; Frings-Meuthen, Petra; Heer, Martina; Mester, Jochen; Liphardt, Anna-Maria (European Journal of Applied Physiology, 2012)
The absence of mechanical loading leads to a prompt increase in bone resorption measured by bone resorption markers. There is high potential that vibration training can positively influence bone metabolism in immobilized subjects, reduce the increase in osteoclastic activity and increase bone formation processes. We investigated whether vibration training at 20 Hz with an amplitude of 2-4 mm influences bone metabolism during immobilization. Eight male subjects (26.4 ± 4.9 years; 78.1 ± 9.5 kg) performed a 14 day bed rest in 6°-head down tilt (HDT). Subjects received vibration training for 2 × 5 min/day or a control intervention without vibration (crossover design). Calcium excretion and bone resorption markers C-telopeptide (CTX) and N-telopeptide (NTX) were analyzed from 24 h urine samples. Bone formation markers, bone alkaline phosphatase (bAP) and procollagen-N propeptide (PINP) were analyzed from fasting blood samples. Our results show an increase in bone resorption very early during HDT bed rest in both interventions (CTX: p < 0.01; NTX: p < 0.001). Vibration training did not have any different effect on bone resorption markers (CTX: p = 0.10; NTX: p = 0.58), bone formation markers (PINP: p = 0.21; bAP: p = 0.12) and calcium excretion (p < 0.64) compared to the control condition. Mere vibration training with 20 Hz for 2 × 5 min/day does not prevent increase in bone resorption as measured with the described methods in our short-term HDT bed rest.
EVALuna2:13505

EMG and heart rate responses decline within 5 days of daily whole-body vibration training with squatting - Rosenberger, Andre; Liphardt, Anna-Maria; Bargmann, Arne; Mueller, Klaus; Beck, Luis; Mester, Joachim; Zange, Jochen (PLoS ONE, 2014)
In this study, we examined the acute effects of a 5-day daily whole-body vibration (WBV) training on electromyography (EMG) responses of the m. rectus femoris and m. gastrocnemius lateralis, heart rate (HR, continuously recorded), and blood lactate levels. The purpose of the study was to investigate the adaptation of muscle activity, heart rate and blood lactate levels during 5 days of daily training. Two groups of healthy male subjects performed either squat exercises with vibration at 20 Hz on a side alternating platform (SE+V, n = 20, age = 31.9±7.5 yrs., height = 178.8±6.2 cm, body mass = 79.2±11.4 kg) or squat exercises alone (SE, n = 21, age = 28.4±7.3 years, height = 178.9±7.4 cm, body mass = 77.2±9.7 kg). On training day 1, EMG amplitudes of the m. rectus femoris were significantly higher (P<0.05) during SE+V than during SE. However, this difference was no longer statistically significant on training days 3 and 5. The heart rate (HR) response was significantly higher (P<0.05) during SE+V than during SE on all training days, but showed a constant decline throughout the training days. On training day 1, blood lactate increased significantly more after SE+V than after SE (P<0.05). On the following training days, this difference became much smaller but remained significantly different. The specific physiological responses to WBV were largest on the initial training day and most of them declined during subsequent training days, showing a rapid neuromuscular and cardiovascular adaptation to the vibration stimulus.
EVALuna2:13504

Establishment and evaluation of a sensor-based method to assess hand function in patients with rheumatoid arthritis - Coppers, Birte; Phutane, Uday; Berisha, Dardan; Tascilar, Koray; Kleyer, Arnd; Simon, David; Bräunig, Johanna; Penner, Johann; Vossiek, Martin; Schönau, Verena; Heinrich, Simon; Bayat, Sara; et al. (conference, World Biomechanics Congress 2022, 2022)

Evaluation of marker-based motion capturing to charactherize basic hand movements in rheumatic patients - Coppers, Birte; Heinrich, Simon; Phutane, Uday; Berisha, Dardan; Tascilar, Koray; Kleyer, Arnd; Simon, David; Bräunig, Johanna; Penner, Johann; Vossiek, Martin; Schönau, Verena; Bayat, Sara; et al. (27th Congress of the European Society of Biomechanics, 2022)

Evaluation of Optical and Radar Based Motion Capturing Technologies for Characterizing Hand Movement in Rheumatoid Arthritis — A Pilot Study - Phutane, Uday; Liphardt, Anna-Maria; Bräunig, Johanna; Penner, Johann; Klebl, Michael; Vossiek, Martin; Kleyer, Arnd; Schett, Georg; Leyendecker, Sigrid (Sensors, 2021)
In light of the state-of-the-art treatment options for patients with rheumatoid arthritis (RA), a detailed and early quantification and detection of impaired hand function is desirable to allow personalized treatment regiments and amend currently used subjective patient reported outcome measures. This is the motivation to apply and adapt modern measurement technologies to quantify, assess and analyze human hand movement using a marker-based optoelectronic measurement system (OMS), which has been widely used to measure human motion. We complement these recordings with data from markerless (Doppler radar) sensors and data from both sensor technologies are integrated with clinical outcomes of hand function. The technologies are leveraged to identify hand movement characteristics in RA affected patients in comparison to healthy control subjects, while performing functional tests, such as the Moberg-Picking-Up Test. The results presented discuss the experimental framework and present the limiting factors imposed by the use of marker-based measurements on hand function. The comparison of simple finger motion data, collected by the OMS, to data recorded by a simple continuous wave radar suggests that radar is a promising option for the objective assessment of hand function. Overall, the broad scope of integrating two measurement technologies with traditional clinical tests shows promising potential for developing new pathways in understanding of the role of functional outcomes for the RA pathology.<br

Experimental-analytical approach to assessing mechanosensitive cartilage blood marker kinetics in healthy adults: Dose-response relationship and interrelationship of nine candidate markers - Mündermann, Annegret; Herger, Simon; Vach, Werner; Liphardt, Anna-Maria; Nüesch, Corina; Egloff, Christian (F1000Research, 2022)
Purpose: To determine the suitability of selected blood biomarkers of articular cartilage as mechanosensitive markers and to investigate the dose-response relationship between ambulatory load magnitude and marker kinetics in response to load. Methods: Serum samples were collected from 24 healthy volunteers before and at three time points after a 30-minute walking stress test performed on three test days. In each experimental session, one of three ambulatory loads was applied: 100% body weight (BW); 80%BW; 120%BW. Serum concentrations of COMP, MMP-3, MMP-9, ADAMTS-4, PRG-4, CPII, C2C and IL-6 were assessed using commercial enzyme-linked immunosorbent assays. A two-stage analytical approach was used to determine the suitability of a biomarker by testing the response to the stress test (criterion I) and the dose-response relationship between ambulatory load magnitude and biomarker kinetics (criterion II). Results. COMP, MMP-3 and IL-6 at all three time points after, MMP-9 at 30 and 60 minutes after, and ADAMTS-4 and CPII at immediately after the stress test showed an average response to load or an inter-individual variation in response to load of up to 25% of pre-test levels. The relation to load magnitude on average or an inter-individual variation in this relationship was up to 8% from load level to load level. There was a positive correlation for the slopes of the change-load relationship between COMP and MMP-3, and a negative correlation for the slopes between COMP, MMP-3 and IL-6 with MMP-9, and COMP with IL6. Conclusions: COMP, MMP-3, IL-6, MMP-9, and ADAMTS-4 warrant further investigation in the context of articular cartilage mechanosensitivity and its role in joint degeneration and OA. While COMP seems to be able to reflect a rapid response, MMP-3 seems to reflect a slightly longer lasting, but probably also more distinct response. MMP-3 showed also the strongest association with the magnitude of load.
CRIS-Team Scopus Importer:2022-03-18
Keywords: Cartilage biomarkers; Cartilage mechanosensitivity; Dose-response relationship; Mechanical loading; Walking stress test

Feasibility of using optoelectronic measurement of hand movement for characterizing hand function in rheumatoid arthritis - Coppers, Birte; Heinrich, Simon; Phutane, Uday; Berisha, Dardan; Tascilar, Koray; Kleyer, Arnd; Simon, David; Bräunig, Johanna; Penner, Johann; Vossiek, Martin; Schönau, Johanna; Bayat, Sara; et al. (75th EULAR (European Alliance of Associations for Rheumatology), European Congress of Rheumatology 2022, 2022)

FRAMEWORK FOR MODULATING AMBULATORY LOAD IN THE CONTEXT OF IN VIVO MECHANOSENSITIVITY OF ARTICULAR CARTILAGE - Muendermann, A.; Herger, S.; Liphardt, Anna-Maria; Vach, W.; Egloff, C.; Nueesch, C. (OSTEOARTHRITIS AND CARTILAGE, 2020)
CRIS-Team WoS Importer:2020-06-02

HAND FUNCTION IS IMPAIRED IN PATIENTS WITH RHEUMATOID ARTHRITIS, PSORIATIC ARTHRITIS, AND PSORIASIS COMPARED TO HEALTHY CONTROLS - Liphardt, Anna-Maria; Liehr, Sonja; Manger, Eva; Bieniek, Lisa; Kleyer, Arnd; Simon, David; Tascilar, Koray; Sticherling, Michael; Rech, Jürgen; Schett, Georg; Hueber, Axel (ANNALS OF THE RHEUMATIC DISEASES, 2019)
CRIS-Team WoS Importer:2019-07-12

Immobilization by 21 days of bed rest results in type II collagen degradation in healthy individuals - Liphardt, Anna-Maria; Elie-Tino, Godonou; Dreiner, Maren; Mündermann, Annegret; Tascilar, Koray; Djalal, Nadja; Heer, Martina; Schett, Georg; Zaucke, Frank; Niehoff, Anja (Osteoarthritis and Cartilage, 2023)
Objective: To investigate the effects of 21 days of bed rest immobilization (with and without exercise and nutrition interventions) on type II collagen biomarker concentrations in healthy individuals. Design: Twelve healthy male participants (age 34.2 ± 8.3 years; body mass index 22.4 ± 1.7 kg/m²) were exposed to 6 days ambulatory baseline data collection (BDC), 21 days head-down-tilt bed rest (HDT, CON) + interventions (HDT + resistive vibration exercise (2 times/week, 25 minutes): RVE; HDT + RVE + whey protein (0.6 g/kg body weight/day) and bicarbonate supplementation (90 mmol KHCO3/day: NeX), and 6 days of re-ambulation (R) in a cross-over designed study. The starting HDT condition was randomized (CON-RVE-NEX, RVE-NEX-CON, NEX-CON-RVE). Blood and urine samples were collected before, during, and after HDT. Serum concentrations (s) of CPII, C2C, C1,2C, and urinary concentrations (u) of CTX-II and Coll2–1NO2 were measured. Results: Twenty-one days of HDT resulted in increased sCPII (p < 0.001), sC2C (p < 0.001), and sC1,2C (p = 0.001) (highest increases: sCPII (+24.2% - HDT5), sC2C (+24.4% - HDT7), sC1,2C (+13.5% - HDT2). sC2C remained elevated at R+1 (p = 0.002) and R+6 (p < 0.001) compared to baseline. NeX led to lower sCPII (p < 0.001) and sC1,2C (p = 0.003) compared to CON. uCTX-II (second void and 24-hour urine) increased during HDT (p < 0.001, highest increase on HDT21: second void +82.8% (p < 0.001); 24-hour urine + 77.8% (p < 0.001). NeX resulted in lower uCTX-II concentrations in 24-hour urine (p = 0.012) compared to CON. Conclusions: Twenty-one days of bed rest immobilization results in type II collagen degradation that does not recover within 6 days of resuming ambulation. The combination of resistive vibration exercise and protein/bicarbonate supplementation minimally counteracted this effect.
CRIS-Team Scopus Importer:2023-12-15
Keywords: Bed rest; Cartilage biomarkers; Collagen metabolism; Immobilization; MNX-study; Type II collagen

Impact of Cytokine Inhibitor Therapy on the Prevalence, Seroconversion Rate, and Longevity of the Humoral Immune Response Against SARS-CoV-2 in an Unvaccinated Cohort - Simon, David; Tascilar, Koray; Kleyer, Arnd; Fagni, Filippo; Krönke, Gerhard; Meder, Christine; Dietrich, Peter; Orlemann, Till; Kliem, Thorsten; Moessner, Johanna; Liphardt, Anna-Maria; Schönau, Verena; et al. (Arthritis and Rheumatology, 2022)
Objective To investigate the impact of biologic disease-modifying antirheumatic drug (bDMARD) treatment on the prevalence, seroconversion rate, and longevity of the humoral immune response against SARS-CoV-2 in patients with immune-mediated inflammatory diseases (IMIDs). Methods Anti-SARS-CoV-2 IgG antibodies were measured in a prospective cohort of health care professional controls and non-health care controls and IMID patients receiving no treatment or receiving treatment with conventional or biologic DMARDs during the first and second COVID-19 waves. Regression models adjusting for age, sex, sampling time, and exposure risk behavior were used to calculate relative risks (RRs) of seropositivity. Seroconversion rates were assessed in participants with polymerase chain reaction (PCR)-positive SARS-CoV-2 infection. Antibody response longevity was evaluated by reassessing participants who tested positive during the first wave. Results In this study, 4,508 participants (2,869 IMID patients and 1,639 controls) were analyzed. The unadjusted RR (0.44 [95% confidence interval (95% CI) 0.31-0.62]) and adjusted RR (0.50 [95% CI 0.34-0.73]) for SARS-CoV-2 IgG antibodies were significantly lower in IMID patients treated with bDMARDs compared to non-health care controls (P < 0.001), primarily driven by treatment with tumor necrosis factor inhibitors, interleukin-17 (IL-17) inhibitors, and IL-23 inhibitors. Adjusted RRs for untreated IMID patients (1.12 [95% CI 0.75-1.67]) and IMID patients receiving conventional synthetic DMARDs (0.70 [95% CI 0.45-1.08]) were not significantly different from non-health care controls. Lack of seroconversion in PCR-positive participants was more common among bDMARD-treated patients (38.7%) than in non-health care controls (16%). Overall, 44% of positive participants lost SARS-CoV-2 antibodies by follow-up, with higher rates in IMID patients treated with bDMARDs (RR 2.86 [95% CI 1.43-5.74]). Conclusion IMID patients treated with bDMARDs have a lower prevalence of SARS-CoV-2 antibodies, seroconvert less frequently after SARS-CoV-2 infection, and may exhibit a reduced longevity of their humoral immune response.
CRIS-Team WoS Importer:2022-04-08

Impact of the digital health application ViViRA on spinal mobility, physical function, quality of life and pain perception in spondyloarthritides patients: a randomized controlled trial - Palm von Alten Blaskowitz, Paloma Alexandra; Liphardt, Anna-Maria; Bouzas, Claudia; Coppers, Birte; Petit, Pascal; Vuillerme, Nicolas; Bundle, Vanessa; Rudolf, Sebastian; Knitza, Johannes; Raimondo, Maria Gabriella; Labinsky, Hannah; Hatscher, Lukas; et al. (Arthritis Research & Therapy, 2024)
Background: Spondyloarthritides (SpAs) are a group of common rheumatic diseases that often cause limited mobility and lower back pain. Physiotherapy is an integral part of treatment, but access to physiotherapy limits treatment success. Digital health applications (DHAs) enable home-based physiotherapy and could significantly improve access for SpAs patients. The aim is to investigate the clinical effects of the DHA ViViRA compared with those of standard physiotherapy. Methods: SpAs patients with chronic back pain were enrolled in a randomized controlled trial. The intervention group received ViViRA DHA, whereas the control group received standard physiotherapy. Pain (verbal rating scale, PAIN-Detect), quality of life (SF-36) and mobility (BASMI) were assessed at baseline and after 12 weeks as the primary outcomes. Results: Data from 59 participants (71.2% female, mean age 45.2 years) were analyzed. The intervention group showed a significant improvement in mobility (average BASMI score: baseline: 1.1 [range 0.7–1.5]; follow-up: 1.0 [range 0.5–1.4]; p = 0.05), whereas the control group showed a significant decrease in mobility (baseline: 1.5 [range 1.1–1.9]; follow-up: 1.8 [range 1.4–2.2]; p = 0.00). The intervention group demonstrated lower pain intensity (VRS pain level at week 3.5 ± 2.8) than did the control group (VRS pain level at week 4.5 ± 2) after 12 weeks. Conclusion: Our results highlight the efficacy of DHAs such as ViViRA in the treatment of lower back pain in SpAs patients. Compared with the current gold standard, physiotherapy, DHA use results in superior outcomes. However, further larger studies are needed to confirm these promising results. Trial registration: The study is registered in the German clinical trial registry (DRKS) under the following ID: DRKS00031254.
CRIS-Team Scopus Importer:2025-02-04
Keywords: DHA; Digital health application; E-Health; Mobility; Physical function; Psoriatic spondylitis; Spondyloarthritides; Spondyloarthropathy; ViViRA

Inclusion of optical marker position data in optimal control simulations of a rigid body model of the human hand - Heinrich, Simon; Coppers, Birte; Liphardt, Anna-Maria; Leyendecker, Sigrid (conference, ECCOMAS - 11th Thematic Conference on Multibody Dynamics, 2023)

Incomplete recovery of bone strength and trabecular microarchitecture at the distal tibia 1 year after return from long duration spaceflight - Gabel, Leigh; Liphardt, Anna-Maria; Hulme, Paul A.; Heer, Martina; Zwart, Sara R.; Sibonga, Jean D.; Smith, Scott M.; Boyd, Steven K. (Scientific Reports, 2022)
Determining the extent of bone recovery after prolonged spaceflight is important for understanding risks to astronaut long-term skeletal health. We examined bone strength, density, and microarchitecture in seventeen astronauts (14 males; mean 47 years) using high-resolution peripheral quantitative computed tomography (HR-pQCT; 61 μm). We imaged the tibia and radius before spaceflight, at return to Earth, and after 6- and 12-months recovery and assessed biomarkers of bone turnover and exercise. Twelve months after flight, group median tibia bone strength (F.Load), total, cortical, and trabecular bone mineral density (BMD), trabecular bone volume fraction and thickness remained − 0.9% to − 2.1% reduced compared with pre-flight (p ≤ 0.001). Astronauts on longer missions (> 6-months) had poorer bone recovery. For example, F.Load recovered by 12-months post-flight in astronauts on shorter (< 6-months; − 0.4% median deficit) but not longer (− 3.9%) missions. Similar disparities were noted for total, trabecular, and cortical BMD. Altogether, nine of 17 astronauts did not fully recover tibia total BMD after 12-months. Astronauts with incomplete recovery had higher biomarkers of bone turnover compared with astronauts whose bone recovered. Study findings suggest incomplete recovery of bone strength, density, and trabecular microarchitecture at the weight-bearing tibia, commensurate with a decade or more of terrestrial age-related bone loss.
CRIS-Team Scopus Importer:2022-07-15

Intensity and longevity of SARS-CoV-2 vaccination response in patients with immune-mediated inflammatory disease: a prospective cohort study. - Simon, David; Tascilar, Koray; Fagni, Filippo; Kleyer, Arnd; Krönke, Gerhard; Meder, Christine; Dietrich, Peter; Orlemann, Till; Mößner, Johanna; Taubmann, Jule; Mutlu, Melek Yalcin; Knitza, Johannes; et al. (The Lancet Rheumatology, 2022)
Background: Concerns have been raised about the reduced immunogenicity of vaccines against SARS-CoV-2 in patients with immune-mediated inflammatory diseases and the higher risk of breakthrough infections. The objective of our study was to investigate the intensity and longevity of SARS-CoV-2 vaccination responses in patients with immune-mediated inflammatory diseases, and to assess the effects of diagnosis, treatment, and adapted vaccination schedules. Methods: SARS-CoV-2 IgG antibody response after SARS-CoV-2 vaccination was measured over time in a large prospective cohort of healthy controls and participants with immune-mediated inflammatory diseases (attending or admitted to affiliated centres) between Dec 15, 2020, and Dec 1, 2021. Cohort participants with immune-mediated inflammatory diseases and control participants with no diagnosis of immune-mediated inflammatory diseases, were eligible for this analysis. Demographic data and disease-specific data were collected using a questionnaire. Humoral response was compared across treatment and disease groups, and with respect to the receipt of additional vaccinations. SARS-CoV-2 antibody response was measured by ELISA using optical density ratio units and modelled over time with age and sex adjustment using mixed-effects models. Using these models, marginal mean antibody titres and marginal risks of a poor response (optical density ratio <1·1) were calculated for each week starting from week 8 after the first vaccination to week 40. Findings: Among 5076 individuals registered, 2535 participants with immune-mediated inflammatory diseases (mean age 55·0 [15·2] years; 1494 [58·9%] women and 1041 [41·1%] men) and 1198 healthy controls (mean age 40·7 [13·5] years; 554 [46·2%] women and 644 [53·8%] men) were included in this analysis. Mean antibody titres were higher in healthy controls compared with people with immune-mediated inflammatory diseases at all timepoints, with a peak antibody response in healthy controls (mean optical density ratio 12·48; 95% CI 11·50-13·53) of more than twice that in participants with immune-mediated inflammatory diseases (5·50; 5·23-5·77; mean difference 6·98; 5·92-8·04). A poor response to vaccination was observed in participants with immune-mediated inflammatory diseases who were taking B-cell inhibitors (peak mean difference from healthy controls 11·68; 10·07-13·29) and T-cell inhibitors (peakmean difference from healthy controls 10·43; 8·33-12·53). Mean differences in antibody responses between different immune-mediated inflammatory diseases were small. Participants with immune-mediated inflammatory diseases who were given a third vaccine dose had higher mean antibody titres than did healthy controls vaccinated with two vaccine doses at 40 weeks after the initial vaccination (mean difference 1·34; 0·01-2·69). Interpretation: People with immune-mediated inflammatory diseases show a lower and less durable SARS-CoV-2 vaccination response and are at risk of losing humoral immune protection. Adjusted vaccination schedules with earlier booster doses or more frequent re-doses, or both, could better protect people with immune-mediated inflammatory diseases. Funding: Deutsche Forschungsgemeinschaft, Bundesministerium für Bildung und Forschung, European Research Council, Innovative Medicine Initiative, Friedrich-Alexander-Universität Erlangen-Nürnberg, Else Kröner-Memorial Foundation.
EVALuna2:506737

Internal vascular anatomy of the human lacrimal gland: A protocol based on cadaver dissection and three-dimensional micro-computed tomography - Singh, Swati; Chopra, Prakshi; Necker, Fabian; Scholz, Michael; Liphardt, Anna-Maria; Schuster, Louis; Paulsen, Friedrich; Bräuer, Lars (Annals of Anatomy-Anatomischer Anzeiger, 2024)
Purpose: To evaluate the feasibility of studying the vascular supply of the orbital and palpebral lobes of the human lacrimal gland using micro-computed tomography (micro-CT) and microscopic dissection. Methods: The lacrimal gland artery of a fresh parasagittalized cadaver head (male, aged 76 years) was infused with a lead oxide-latex mixture near the occipital pole of the gland. The entire lacrimal gland was imaged using micro-CT and 3D cinematic rendering (CR) and then dissected under a surgical microscope. Results: Micro-CT and CR images showed well-demarcated internal vascular branches of the lacrimal artery and their distribution within the orbital and palpebral lobes. The entire course of the artery and its branches could be visualized by CR and microscopic dissection, with the former showing better spatial orientation and finer branching. The main artery runs along the free edge of the aponeurosis of the levator palpebrae superior muscle and lies in the isthmus portion of the gland (between the orbital and palpebral lobes). The branches of the main lacrimal artery include one branch to the orbital adipose tissue just before entering the gland, two branches to the orbital lobe (medial and lateral), and two branches to the palpebral lobe (medial and lateral). The main artery terminates as palpebral and orbital lobe branches in the lateral half of the lacrimal gland. Conclusion: Latex and contrast-enhanced micro-CT is very well suited to visualize the vascular anatomy of the lacrimal artery within the gland. A large number of lacrimal gland examinations using the method presented here are required to demonstrate and understand the variability of the vascular anatomy of the human lacrimal gland.
CRIS-Team Scopus Importer:2024-01-19
Keywords: Anatomy; CT; Dry eye disease; Lacrimal artery; Lacrimal gland

In vivo models of human articular cartilage mechanosensitivity - Mündermann, Annegret; Liphardt, Anna-Maria; Herger, Simon (Elsevier, 2023)
Mechanical load is important for the development, maintenance, and regeneration of healthy musculoskeletal tissues, including articular cartilage. Elucidating the association between mechanical load applied to articular cartilage and changes in articular cartilage metabolism in the context of articular cartilage health will not only allow evaluating the role of mechanical loading in the pathophysiology of diseases affecting articular cartilage but also broaden the understanding of the effects of mechanical loading on joint health or their role in fostering articular cartilage regeneration after injury. In this chapter, we provide a critical overview of existing human in vivo models for articular cartilage mechanosensitivity. The material is based on studies investigating the response of biochemical markers of articular cartilage health to acute stimuli and interventions, including loading stress, immobilization, microgravity, and medical interventions, in healthy and pathological populations.
CRIS-Team Scopus Importer:2023-11-24
Keywords: exercise; human model; In vivo; joint load; stress test; tissue metabolism

Load-induced blood marker kinetics in patients with medial knee compartment osteoarthritis are associated with accumulated load and patient reported outcome measures - Mündermann, Annegret; Nüesch, Corina; Herger, Simon; Liphardt, Anna-Maria; Chammartin, Frédérique; De Pieri, Enrico; Egloff, Christian (F1000Research, 2024)
Background: This study aimed to quantify the mechanoresponse of 10 blood marker candidates for joint metabolism to a walking stress test in patients with knee osteoarthritis and to determine the association among marker kinetics and with accumulated load and patient reported outcomes. Methods: 24 patients with knee osteoarthritis completed questionnaires, and a 30-minute walking stress test with six blood serum samples and gait analysis. Concentrations of cartilage oligomeric matrix protein (COMP), matrix metalloproteinases (MMP)-1, -3, and -9, epitope resulting from cleavage of type II collagen by collagenases (C2C), type II procollagen (CPII), interleukin (IL)-6, proteoglycan (PRG)-4, A disintegrin and metalloproteinase with thrombospondin motifs (ADAMTS)-4, and resistin were determined by enzyme-linked immunosorbent assays, Joint load (moments and compartmental forces) was estimated using musculoskeletal modeling using gait analysis data. Results: COMP and MMP-3 showed an immediate increase after the walking stress followed by a decrease. MMP-9 and resistin showed a delayed decrease below pre-stress levels. ∆COMP correlated with ∆MMP-3 for most time points. ∆MMP-9 correlated with ∆resistin for most time points. The load-induced increase in blood marker levels correlated among blood markers and time points. C2C and resistin correlated positively and C2C/CPII and MMP2 correlated negatively with load during gait. Immediate relative ∆CPII and ∆MMP1 and delayed relative ∆COMP, ∆IL6, ∆C2C, ∆CPII, ∆MMP1 and ∆MMP3 correlated with the load accumulated during the walking stress. Baseline C2C levels correlated with Knee Osteoarthritis Outcome Score (KOOS) subscales and load-induced changes in MMP-3 with KOOS and Short Form 36 quality of life subscores (P<0.05). Conclusions: The distinct and differentiated physiological response to the walking stress depends on accumulated load and appears relevant for patient reported osteoarthritis outcome and quality of life and warrants further investigation in the context of disease progression. ClinicalTrials.gov registration: https://clinicaltrials.gov/ct2/show/NCT02622204?term=NCT02622204&draw=2&rank=1 NCT02622204
CRIS-Team Scopus Importer:2024-06-28
Keywords: ambulatory load; articular cartilage; in vivo mechanoresponse; Knee osteoarthritis; PROMs; serum biomarkers; stress test

Load-induced changes in articular cartilage biomarkers before and after a high tibial osteotomy in patients with medial compartment knee osteoarthritis - Mundermann, A.; Liphardt, Anna-Maria; Pagenstert, G.; Egloff, C.; Nueesch, C. (BRITISH JOURNAL OF SURGERY, 2019)
CRIS-Team WoS Importer:2019-05-24

Load-induced changes in articular cartilage biomarkers before and after high tibial osteotomy in patients with medial knee osteoarthritis - Mundermann, Annegret; Liphardt, Anna-Maria; Egloff, Christian; Pagenstert, Geert; Nuesch, Corina (SWISS MEDICAL WEEKLY, 2019)
CRIS-Team WoS Importer:2019-07-19

Locomotion replacement exercise cannot counteract cartilage biomarker response to 5 days of immobilization in healthy adults - Liphardt, Anna-Maria; Muendermann, Annegret; Heer, Martina; Achtzehn, Silvia; Niehoff, Anja; Mester, Joachim (Journal of Orthopaedic Research, 2020)
Biomarkers of cartilage metabolism are sensitive to changes in the biological and mechanical environment and can indicate early changes in cartilage homeostasis. The purpose of this study was to determine if a daily locomotion replacement program can serve as a countermeasure for changes in cartilage biomarker serum concentration caused by immobilization. Ten healthy male subjects (mean ± 1 standard deviation; age: 29.4 ± 5.9 years; body mass: 77.7 ± 4.1 kg) participated in the crossover 5-day bed rest study with three interventions: control (CON), standing (STA), and locomotion replacement training (LRT). Serum samples were taken before, during, and after bed rest. Biomarker concentrations were measured using commercial enzyme-linked immunosorbent assays. Cartilage oligomeric matrix protein (COMP) levels after 24 hours of bed rest decreased independently of the intervention (−16.8% to −9.8%) and continued to decrease until 72 hours of bed rest (minimum, −23.2% to −20.6%). LRT and STA did not affect COMP during bed rests (P =.056) but there was a strong tendency for a slower decrease with LRT (−9.4%) and STA (−11.7%) compared with CON (−16.8%). MMP-3 levels decreased within the first 24 hours of bed rest (CON: −22.3%; STA: −14.7%; LRT: −17%) without intervention effect. Both COMP and MMP-3 levels recovered to baseline levels during the 6-day recovery period. MMP-1, MMP-9, and TNF-α levels were not affected by immobilization or intervention. COMP and MMP-3 are mechano-sensitive cartilage biomarkers affected by immobilization, and simple interventions such as standing upright or LRT during bed rest cannot prevent these changes. Clinical significance: simple locomotion interventions cannot prevent cartilage biomarker change during bed rest.
CRIS-Team Scopus Importer:2020-07-31
Keywords: bed rest; cartilage biomarkers; cartilage degeneration; cartilage oligomeric matrix protein; immobilization

LONG-TERM HUMORAL RESPONSE TO SARS-COV-2 VACCINATION IN PATIENTS WITH IMMUNE-MEDIATED INFLAMMATORY DISEASE - Tascilar, Koray; Simon, David; Kleyer, Arnd; Fagni, Filippo; Krönke, Gerhard; Meder, Christine; Dietrich, Peter; Orlemann, Till; Kliem, Thorsten; Moessner, J.; Liphardt, Anna-Maria; Schönau, Verena; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2022)
CRIS-Team WoS Importer:2022-11-04

LONG-TERM REPEATABILITY OF CARTILAGE OLIGOMERIC MATRIX PROTEIN KINETICS IN RESPONSE TO WALKING STRESS - Herger, S.; Liphardt, Anna-Maria; Egloff, C.; Corina, N.; Mundermann, A. (OSTEOARTHRITIS AND CARTILAGE, 2021)
CRIS-Team WoS Importer:2021-05-21

Markerless RGB-D Hand Pose Estimation for Activity Monitoring of Musculoskeletal Diseases - Wirth, Vanessa; Liphardt, Anna-Maria; Coppers, Birte; Bräunig, Johanna; Heinrich, Simon; Leyendecker, Sigrid; Kleyer, Arnd; Schett, Georg; Vossiek, Martin; Egger, Bernhard; Stamminger, Marc (IEEE-EMBS International Conference on Biomedical and Health Informatics (BHI’23), 2023)

Marker position uncertainty in joint angle analysis for normal human gait — A new error-modelling approach - Scheiterer, Eduard; Heinrich, Simon; Liphardt, Anna-Maria; Leyendecker, Sigrid (Biomedical Signal Processing and Control, 2024)

MECHANOSENSITIVE BLOOD MARKERS AND THEIR INTERRELATION IN PATIENTS WITH MEDIAL COMPARTMENT KNEE OSTEOARTHRITIS - Muendermann, A.; Nueesch, C.; Chammartin, F.; Simon, H.; Liphardt, Anna-Maria; Egloff, C. (OSTEOARTHRITIS AND CARTILAGE, 2021)
CRIS-Team WoS Importer:2021-05-21

Musculoskeletal research in human space flight – unmet needs for the success of crewed deep space exploration - Liphardt, Anna-Maria; Fernandez-Gonzalo, Rodrigo; Albracht, Kirsten; Rittweger, Jörn; Vico, Laurence (npj microgravity, 2023)
Based on the European Space Agency (ESA) Science in Space Environment (SciSpacE) community White Paper “Human Physiology – Musculoskeletal system”, this perspective highlights unmet needs and suggests new avenues for future studies in musculoskeletal research to enable crewed exploration missions. The musculoskeletal system is essential for sustaining physical function and energy metabolism, and the maintenance of health during exploration missions, and consequently mission success, will be tightly linked to musculoskeletal function. Data collection from current space missions from pre-, during-, and post-flight periods would provide important information to understand and ultimately offset musculoskeletal alterations during long-term spaceflight. In addition, understanding the kinetics of the different components of the musculoskeletal system in parallel with a detailed description of the molecular mechanisms driving these alterations appears to be the best approach to address potential musculoskeletal problems that future exploratory-mission crew will face. These research efforts should be accompanied by technical advances in molecular and phenotypic monitoring tools to provide in-flight real-time feedback.
CRIS-Team Scopus Importer:2023-02-10

Objective and subjective hand function reflect grade of tenosynovitis in patients with psoriasis and psoriatic arthritis - Coppers, Birte; Bayat, Sara; Elie-Tino, Godonou; Valor-Mendez, Larissa; Simon, David; Corte, Giulia; Tascilar, Koray; Hueber, Axel; Bohr, Daniela; Schönau, Verena; Sticherling, Michael; Schett, Georg; et al. (poster, Deutsche Gesellschaft für Rheumatologie Kongress, 2023)

On the inclusion of motion capture data in optimal control simulations of the human hand - Heinrich, Simon; Coppers, Birte; Liphardt, Anna-Maria; Leyendecker, Sigrid (conference, 18th International Symposium on Computer Methods in Biomechanics and Biomedical Engineering, 2023)

Optimal Control Simulation of Full Hand Flexion MovementsExploiting Optical Marker Tracking - Heinrich, Simon; Coppers, Birte; Liphardt, Anna-Maria; Leyendecker, Sigrid (conference, Scientific Meetings of ANZSB & ANZORS, 2024)

PATIENTS AT RISK FOR RA SHOW THE SAME AMOUNT OF ACUTE SOLUBLE CARTILAGE DEGRADATION MARKERS AFTER PHYSICAL ACTIVITY COMPARED TO PATIENTS WITH ESTABLISHED RA - Bleckwedel-Rolack, Lisa Lena Kathrein; Tascilar, Koray; Nees, Veronika; Hühne, Julia; Hueber, A.; Rech, Jürgen; Schett, Georg; Kleyer, Arnd; Liphardt, Anna-Maria (ANNALS OF THE RHEUMATIC DISEASES, 2021)
CRIS-Team WoS Importer:2021-09-24

POS0494 Fear Of Movement Affects Range Of Motion During Repeated Basmi Exercises Assessed By State-Of-The-Art Motion Capture Techniques - Loy, N.; Blazek, V.; Jukic, Elke; Fleischmann, Martha Elisa; Coppers, Birte; Hübner, Julian; Iqbal, M.; Heinrich, Simon; Scheiterer, Eduard; Leyendecker, Sigrid; Greenfield, Julia; Labinski, H.; et al. (Annals of the Rheumatic Diseases, 2024)
Background: Quantification of spinal mobility in chronic axial spondyloarthritis (axSpA) is an important component of disease assessment and is currently assessed using the clinical Bath Ankylosing Spondylitis Metrology Index (BASMI). Functional movement-based outcome measures are dependent on a number of secondary factors and, in particular, the impact of fear of movement on BASMI performance in axSpA patients is currently unknown. Objectives: To investigate the association of range of motion (RoM) for repeated BASMI exercises detected by inertial measurement units (IMU) and optical-measurement system (OMS) motion capture with fear of movement by Tampa Scale of Kinesophobia 17 (TSK) [1)] in axSpA patients. Methods: AxSpa patients (Internal Medicine 3, Universitätsklinikum Erlangen) and healthy controls (HC) were asked to fill out the TSK and BASMI was performed and scored for three repetitions for each task by a trained physician. The BASMI tasks were performed a second time on the same day as the clinical assessment using OMS. Fifty-four retro-reflective markers and 16 IMU devices (myoMOTION by Noraxon, Scottsdale, USA) were placed on defined anatomic sites (Figure 1) and marker motion was detected with 11 infrared cameras (Oqus 7+, Qualisys, Göteborg, Sweden). BASMI values for each task were analysed in distance (cm) or degree of rotation. A correlation matrix was used to assess the relationship between TSK score and BASMI task 5 (lateral neck flexion in degrees) values from the OMS and IMU data, using the Pearson product moment correlation. Exact BASMI values in degrees and clinical BASMI value per group are reported as means ± standard deviation (SD). Results: Fifty participants were included in the study (30 axSpa patients (12/16 male/female, age: 41.9 (SD 12.3), C-reactive protein: 5.2 (13.8) mg/l and visual analog scale (VAS) global: 4.1 (SD 2.7)) and 20 HC (9/11 male/female, age: 28.4 (SD 3.7) and VAS global 0.1 (SD 0.29)). Measurements from two patients were excluded due to failed IMU und OMS data post-processing, resulting in 28 patients for this analysis. Correlation results between the exact BASMI-5 scores (degree of rotation) for each of the three repetitions and the TSK scores are presented in Table 1. AxSpA patients showed a positive, but not significant (p>0.05) correlation between OMS and TSK score, and a positive, significant (p<0.05) correlation between IMU and TSK score data. The correlation remained stable over the three repetitions. For the IMU data, significant correlations with the tendency of higher values over each of the three repetitions for both groups were observed. In contrast, the HC values showed a negative correlation for both the OMS and IMU values with the TSK score. An increase over the three repetitions in the negative correlation can be seen for both measurement systems. Conclusion: Our results suggest positive relationship between fear of movement and cervical movement restriction in axSpa patients. In addition, axSpA patients tended to achieve higher levels of mobility on repetition of exercise than at baseline. This influence of fear of movement on functional outcomes is especially visible in the IMU data for the axSpa patients. In contrast, the relationship between fear of movement and cervical movement tends to be negative for HC, suggesting that in healthy subjects fear of movement assessed over the TSK does not impact the objectively measured cervical mobility. Further analysis will include a wider range of BASMI tasks to identify movements that might be particularly prone to impairments due to fear of movemen

Preflight Biomarkers of Bone Remodelling Predict Bone Loss on Long-Duration Spaceflight - Gabel, Leigh; Hulme, Paul; Liphardt, Anna-Maria; Heer, Martina; Zwart, Sara; Sibonga, Jean; Smith, Scott; Boyd, Steven (JOURNAL OF BONE AND MINERAL RESEARCH, 2020)
CRIS-Team WoS Importer:2021-01-08

Pre-flight exercise and bone metabolism predict unloading-induced bone loss due to spaceflight - Gabel, Leigh; Liphardt, Anna-Maria; Hulme, Paul A.; Heer, Martina; Zwart, Sara R.; Sibonga, Jean D.; Smith, Scott M.; Boyd, Steven (British Journal of Sports Medicine, 2021)
Objectives: Bone loss remains a primary health concern for astronauts, despite in-flight exercise. We examined changes in bone microarchitecture, density and strength before and after long-duration spaceflight in relation to biochemical markers of bone turnover and exercise. Methods: Seventeen astronauts had their distal tibiae and radii imaged before and after space missions to the International Space Station using high-resolution peripheral quantitative CT. We estimated bone strength using finite element analysis and acquired blood and urine biochemical markers of bone turnover before, during and after spaceflight. Pre-flight exercise history and in-flight exercise logs were obtained. Mixed effects models examined changes in bone and biochemical variables and their relationship with mission duration and exercise. Results: At the distal tibia, median cumulative losses after spaceflight were -2.9% to -4.3% for bone strength and total volumetric bone mineral density (vBMD) and -0.8% to -2.6% for trabecular vBMD, bone volume fraction, thickness and cortical vBMD. Mission duration (range 3.5-7 months) significantly predicted bone loss and crewmembers with higher concentrations of biomarkers of bone turnover before spaceflight experienced greater losses in tibia bone strength and density. Lower body resistance training volume (repetitions per week) increased 3-6 times in-flight compared with pre-spaceflight. Increases in training volume predicted preservation of tibia bone strength and trabecular vBMD and thickness. Conclusions: Findings highlight the fundamental relationship between mission duration and bone loss. Pre-flight markers of bone turnover and exercise history may identify crewmembers at greatest risk of bone loss due to unloading and may focus preventative measures.
CRIS-Team Scopus Importer:2021-03-05
Keywords: biochemistry; biomechanics; bone; exercise; osteoporosis

Preventing Disuse-Induced Osteoporosis - Leyendecker, Sigrid; Liphardt, Anna-Maria; Pivonka, Peter; Martelli, Saulo (poster, Bavaria-Queensland Research Alliance, 2025)

Quality control for bone quality parameters affected by subject motion in high-resolution peripheral quantitative computed tomography - Pauchard, Yves; Liphardt, Anna-Maria; Macdonald, Heather M.; Hanley, David A.; Boyd, Steven K. (Bone, 2012)
Subject motion during high-resolution peripheral quantitative computed tomography (HR-pQCT) causes image artifacts that affect morphological analysis of bone quality. The aim of our study was to determine effectiveness of techniques for quality control in the presence of motion in vivo including automated and manual approaches. First, repeatability of manual grading was determined within and between laboratories. Given proper training using a standardized scale and training images (provided by the manufacturer), we found that manual grading is suitable for repeatable image quality grading within and across sites (ICC>0.7). Both a new automated technique providing motion measures based on projection moments, and traditional manual grading (1=best, 5=worst) were subsequently used to assess subject data for motion in N=137 image pairs (scan/re-scan) from the Canadian Multicentre Osteoporosis Study (CaMos) Calgary cohort. High quality image pairs were selected and measurement precision was estimated by calculating the coefficient of variation (CV). Consistent with previous data, density parameters (e.g. total bone mineral density) are more robust than structural (e.g. trabecular number) or finite element parameters (e.g. failure load). To obtain acceptable measurement precision, images should not exceed a manual grading of 3 (on a scale from 1 to 5) or an automatic (?(T)) grading of 1.2. Automatic and manual grading provide comparable quality control, but the advantage of the automated technique is its ability to provide a motion value at scan time (providing a basis for real time decision regarding re-scan requirements), and the assessment is objective. Notably, automatic motion measurement can be performed retrospectively based on original scan data, and is therefore well suited for multi-center studies as well as any research where objective quality control is paramount.
EVALuna2:13508

Relationship between different serum cartilage biomarkers in the acute response to running and jumping in healthy male individuals - Maren, Dreiner; Tobias, Munk; Frank, Zaucke; Liphardt, Anna-Maria; Anja, Niehoff (Scientific Reports, 2022)
The effect of physical activity on serum cartilage biomarkers is largely unknown. The purpose of the study was to systematically analyze the acute effect of two frequently used exercise interventions (running and jumping) on the correlation of seven serum biomarkers that reflect cartilage extracellular matrix metabolism. Fifteen healthy male volunteers (26 ± 4 years, 181 ± 4 cm, 77 ± 6 kg) participated in the repeated measurement study. In session 1, the participants accomplished 15 × 15 series of reactive jumps within 30 min. In session 2, they ran on a treadmill (2.2 m/s) for 30 min. Before and after both exercise protocols, four blood samples were drawn separated by 30 min intervals. Serum concentrations of seven biomarkers were determined: COMP, MMP-3, MMP-9, YKL-40, resistin, Coll2-1 and Coll2-1 NO2. All biomarkers demonstrated an acute response to mechanical loading. Both the COMP and MMP-3 responses were significantly (p = 0.040 and p = 0.007) different between running and jumping (COMP: jumping + 31%, running + 37%; MMP-3: jumping + 14%, running + 78%). Resistin increased only significantly (p < 0.001) after running, and Coll2-1 NO2 increased significantly (p = 0.001) only after jumping. Significant correlations between the biomarkers were detected. The relationships between individual serum biomarker concentrations may reflect the complex interactions between degrading enzymes and their substrates in ECM homeostasis.
CRIS-Team Scopus Importer:2022-04-29

RESTING SERUM CARTILAGE OLIGOMERIC MATRIX PROTEIN CONCENTRATION - THE ROLE OF AGE AND ANTERIOR CRUCIATE LIGAMENT INJURY - Herger, S.; Aghlmandi, S.; Liphardt, Anna-Maria; Nueesch, C.; Egloff, C.; Muendermann, A. (OSTEOARTHRITIS AND CARTILAGE, 2022)
CRIS-Team WoS Importer:2022-04-22

Rising stars in environmental, aviation and space physiology: 2022 - Saveko, Alina; Liphardt, Anna-Maria; Washio, Takuro; Petersen, Lonnie G.; Custaud, Marc Antoine (Frontiers in Physiology, 2023)
CRIS-Team Scopus Importer:2023-07-07
Keywords: countermeasures; deconditioning; gravitational physiology; integrative physiology; weightlessness

Sclerostin and DKK1 levels during 14 and 21 days of bed rest in healthy young men - Frings-Meuthen, P; Boehme, G; Liphardt, Anna-Maria; Baecker, N; Heer, M; Rittweger, J (The Journal of Musculoskeletal and Neuronal Interactions, 2013)
Wnt signaling pathway may be crucial in the pathogenesis of disuse-induced bone loss. Sclerostin and DKK1, antagonists of the Wnt signaling pathway, were assessed during immobilization by bed rest in young, healthy people.Two bed rest studies were conducted at the German Aerospace Center in Cologne. 14 days of 6° head-down-tilt bed rest were applied to eight healthy young male test subjects in study 1 and 21 days of head-down-tilt bed rest to seven healthy male subjects in study 2.Sclerostin levels increased in both studies during bed rest (study 1, 0.64±0.05 ng/ml to 0.69±0.04 ng/ml, P=0.014; study 2, 0.42±0.04 ng/ml to 0.47±0.04 ng/ml, P=0.008) and they declined at the end of the 14- and 21-day bed rest periods. DKK1 decreased during the bed rest period in study 1 (P<0.001) but increased during bed rest in study 2 (P=0.006). As expected, bone formation marker PINP decreased (study 1, P=0.013; study 2, P<0.001) and bone resorption marker NTX increased during bed rest (P<0.001).Data suggest that the Wnt signaling pathway is involved in disuse-induced bone loss in young, healthy humans.
EVALuna2:13506

Self-collection of capillary blood and saliva to determine COVID-19 vaccine immunogenicity in patients with immune-mediated inflammatory diseases and health professionals - Schmetzer, Caroline; Vogt, Ekaterina; Stellar, Laura; Godonou, Elie-Tino; Liphardt, Anna-Maria; Muehlensiepen, Felix; Vuillerme, Nicolas; Hueber, Axel; Kleyer, Arnd; Krönke, Gerhard; Schett, Georg; Simon, David; et al. (Frontiers in Public Health, 2022)
Introduction: Being able to independently determine vaccine induced antibody responses by minimal-invasive methods is of great interest to enable a flexible and effective vaccination strategy. This study aimed to evaluate (1) the accuracy, feasibility, usability and acceptability of capillary blood and saliva self-sampling to determine SARS-CoV-2 antibody responses in patients with immune-mediated inflammatory diseases (IMIDs) and health professionals (HP). Methods: IMID patients and HP having received two doses of SARS-CoV-2 vaccines, self-collected capillary blood (Tasso+) and saliva samples. Capillary samples were considered interchangeable with venous blood if three criteria were met: Spearman's correlation coefficient (r) > 0.8, non-significant Wilcoxon signed-rank test (i.e., p > 0.05), and a small bias or 95% of tests within 10% difference through Bland-Altman. Participants completed a survey to investigate self-sampling usability (system usability scale; SUS) and acceptability (net promoter score; NPS). Study personnel monitored correct self-sampling completion and recorded protocol deviations. Results: 60 participants (30 IMID patients and 30 HP) were analyzed. We observed interchangeability for capillary samples with an accuracy of 98.3/100% for Anti-SARS-CoV-2 IgG/IgA antibodies, respectively. Fifty-eight capillary blood samples and all 60 saliva samples were successfully collected within the first attempt. Usability of both self-sampling procedures was rated as excellent, with significantly higher saliva ratings (p < 0.001). Capillary self-sampling was perceived as significantly (p < 0.001) less painful compared to traditional venous blood collection. Participants reported a NPS for capillary and saliva self-sampling of +68% and +63%, respectively. The majority of both groups (73%) preferred capillary self-sampling over professional venous blood collection. Conclusion: Our results indicate that capillary self-sampling is accurate, feasible and preferred over conventional venous blood collection. Implementation could enable easy access, flexible vaccination monitoring, potentially leading to a better protection of vulnerable patient groups. Self-collection of saliva is feasible and safe however more work is needed to determine its application in clinical practice.
CRIS-Team Scopus Importer:2022-11-11
Keywords: capillary blood; COVID-19; remote care; self-collection; self-sampling; telehealth

Sensitivity of serum concentration of cartilage biomarkers to 21-days of bed rest - Liphardt, Anna-Maria; Mündermann, Annegret; Andriacchi, Thomas P.; Achtzehn, Silvia; Heer, Martina; Mester, Joachim (Journal of Orthopaedic Research, 2017)
The objective of the study was to test the hypothesis that serum levels of cartilage oligomeric matrix protein (COMP) would decrease and serum levels of tumor-necrosis factor alpha (TNF-?) and selected matrix metalloproteinases (MMPs) would increase in response to bed rest (BR) and that these changes are unaffected by the intake of potassium bicarbonate or whey protein. Seven and 9 healthy male subjects participated in two 21-day 6° head down tilt crossover BR-studies with nutrition interventions. Serum samples were taken before, during, and after BR and biomarker concentrations were measured using commercial enzyme-linked immunosorbent assays. MMP-3 during BR was significantly lower than at baseline (reduction greater 20%; P<0.001). MMP-3 increased significantly from 14 to 21 days of BR (+7%; P=0.049). COMP during BR was significantly lower than at baseline (reduction greater 20%; P<0.001). MMP-3 and COMP returned to baseline within one day after BR. MMP-9 on day 3 of BR was significantly lower than at baseline (-31%; P<0.033) and on days 3, 5 and 14 of BR significantly lower than at the end of and after BR (reduction greater 35%; P<0.030). The nutritional countermeasures did not affect these results. The observed changes in cartilage biomarkers may be caused by altered cartilage metabolism in response to the lack of mechanical stimulus during BR and inflammatory biomarkers may play a role in changes in biomarker levels.Immobilization independently from injury can cause altered cartilage biomarker concentration. This article is protected by copyright. All rights reserved.
EVALuna2:13500

Sensor-assessed grasping time as a biomarker of functional impairment in rheumatoid arthritis - Coppers, Birte; Heinrich, Simon; Tascilar, Koray; Phutane, Uday; Kleyer, Arnd; Simon, David; Bräunig, Johanna; Penner, Johann; Vossiek, Martin; Schönau, Verena; Bayat, Sara; Schett, Georg; et al. (Scientific Reports, 2025)
Quantifying physical impairment in rheumatoid arthritis (RA) is important to determine disease burden and disability. Therefore, we aimed to define hand function impairments in RA patients using an opto-electronic measurement system (OMS). In this cross-sectional pilot study, spatio-temporal and hand segment data were collected during the fine motor skill Moberg Picking-Up Test (MPUT) and two elementary hand movement tasks in RA patients and healthy controls (HC) using a marker-based OMS. The duration of two MPUT movement phases (grasping, transporting 12 objects) and kinematic characteristics during the elementary movements were evaluated. We analyzed between-group differences using linear mixed-effects models accounting for within-participant clustering of hands and adjusting for age and sex. Measurements were obtained from 24 RA and 23 HC. The mean duration of the grasping phase of MPUT was longer in RA patients compared to HC while transporting times were identical, showing a significant group-phase interaction (p < 0.001). Interphalangeal joint angle ratios were similar in RA and HC (p > 0.05) with a lower ratio in both groups for the task thumb-finger opposition compared to flexion of joints. In RA patients especially grasping objects was impaired, and performance time for a subset of objects may serve as a quantitative biomarker of functional impairment.<br
CRIS-Team Scopus Importer:2025-03-14
Keywords: Biomarkers; Biomechanics; Fine-motor skills; Hand; Rheumatoid arthritis

SERUM CARTILAGE BIOMARKERS IN RESPONSE TO 21 DAYS BED REST WITH EXERCISE AND NUTRITION COUNTERMEASURES - Dreiner, M.; Zaucke, F.; Muendermann, A.; Liphardt, Anna-Maria; Niehoff, A. (OSTEOARTHRITIS AND CARTILAGE, 2022)
CRIS-Team WoS Importer:2022-04-22

Serum extracellular matrix biomarkers in rheumatoid arthritis, psoriatic arthritis and psoriasis and their association with hand function - Port, Helena; Coppers, Birte; Tragl, Sonja; Manger, Eva; Niemiec, Lisa Maria; Bayat, Sara; Simon, David; Fagni, Filippo; Corte, Giulia; Bay-Jensen, Anne Christine; Tascilar, Koray; Hueber, Axel; et al. (Scientific Reports, 2025)
Inflammatory arthritis, including rheumatoid arthritis and psoriatic arthritis, is characterized by physical function impairment. This becomes apparent even before arthritis onset, as in psoriasis (PsO). Chronic inflammation triggers an accelerated remodeling of the extracellular matrix (ECM), resulting in released ECM fragments detectable in blood. We aimed to investigate levels of blood-based ECM biomarkers in patients with RA, PsA, PsO, and healthy controls and to explore the association of ECM biomarkers with hand function impairments. Patients with RA (n = 85), PsA (n = 115), PsO (n = 102) and controls (n = 110) were included in this cross-sectional study. ECM catabolic (C1M, C2M, C3M, C4M, PRO-C4, C6M, ARG), formation (PRO-C1, PRO-C3, PRO-C6) and inflammation biomarkers (VICM) were measured in serum from all patients. Objective hand function (fine motor skills (Moberg-Picking-Up Test), isometric grip strength (dynamometer) and patient-perceived hand function (Michigan Hand Questionnaire (MHQ)) were assessed. Patients with RA and PsA received treatment with disease-modifying anti-rheumatic drugs. VICM levels were higher in RA, PsA, and PsO than in controls (p < 0.0001). PsA and PsO showed higher C4M levels compared to controls (p < 0.0001, p < 0.0001), while C6M was lower in patients with RA, PsA and PsO than in controls (p < 0.0001, p < 0.001, p < 0.01). PsO presented with higher levels of C1M compared to controls and to RA (p < 0.001 and p < 0.0001). PRO-C6 correlated negatively with MHQ (ρ = -0.39, p < 0.01) and grip strength (ρ = -0.31, p < 0.05) in PsO, while only weak correlations were observed between biomarkers and hand function scores for RA and PsA patients (all ρ < ± 0.2–0.3). Patients with RA, PsA, and PsO showed significant alterations in ECM remodeling biomarkers. Especially PsA and PsO had higher levels of inflammatory biomarkers compared to RA and controls, likely due to modulation by treatment. Predominantly in PsO, ECM formation biomarkers were associated with hand function impairments.<br
Keywords: Extracellular matrix; Biochemical markers; Rheumatoid arthritis; Psoriatic arthritis; Psoriasis; Hand function

SERUM KINETICS OF CARTILAGE BIOLOGICAL MARKERS IN RESPONSE TO IMMOBILIZATION AND PHYSICAL EXERCISE, AND THE POTENTIAL ROLE OF CGS IN THIS CONTEXT - Liphardt, Anna-Maria; Mundermann, A. (OSTEOPOROSIS INTERNATIONAL, 2019)
CRIS-Team WoS Importer:2019-08-02

ShaRPy: Shape Reconstruction and Hand Pose Estimation from RGB-D with Uncertainty - Wirth, Vanessa; Liphardt, Anna-Maria; Coppers, Birte; Bräunig, Johanna; Heinrich, Simon; Leyendecker, Sigrid; Kleyer, Arnd; Schett, Georg; Vossiek, Martin; Egger, Bernhard; Stamminger, Marc (Proceedings of the IEEE/CVF International Conference on Computer Vision (ICCV) Workshops, 2023)
Despite their potential, markerless hand tracking technologies are not yet applied in practice to the diagnosis or monitoring of the activity in inflammatory musculoskeletal diseases. One reason is that the focus of most methods lies in the reconstruction of coarse, plausible poses, whereas in the clinical context, accurate, interpretable, and reliable results are required. Therefore, we propose ShaRPy, the first RGB-D Shape Reconstruction and hand Pose tracking system, which provides uncertainty estimates of the computed pose, e.g., when a finger is hidden or its estimate is inconsistent with the observations in the input, to guide clinical decision-making. Besides pose, ShaRPy approximates a personalized hand shape, promoting a more realistic and intuitive understanding of its digital twin. Our method requires only a light-weight setup with a single consumer-level RGB-D camera yet it is able to distinguish similar poses with only small joint angle deviations in a metrically accurate space. This is achieved by combining a data-driven dense correspondence predictor with traditional energy minimization. To bridge the gap between interactive visualization and biomedical simulation we leverage a parametric hand model in which we incorporate biomedical constraints and optimize for both, its pose and hand shape parameters. We evaluate ShaRPy on a keypoint detection benchmark and show qualitative results of hand function assessments for activity monitoring of musculoskeletal diseases.
Keywords: Musculoskeletal diseases; Hand Pose and Shape Estimation; Uncertainty Estimation; Hand Tracking

Short-term Response of Serum Cartilage Oligomeric Matrix Protein to Different Types of Impact Loading Under Normal and Artificial Gravity - Dreiner, Maren; Willwacher, Steffen; Kramer, Andreas; Kümmel, Jakob; Frett, Timo; Zaucke, Frank; Liphardt, Anna-Maria; Gruber, Markus; Niehoff, Anja (Frontiers in Physiology, 2020)
Microgravity during long-term space flights induces degeneration of articular cartilage. Artificial gravity through centrifugation combined with exercise has been suggested as a potential countermeasure for musculoskeletal degeneration. The purpose of this study was to investigate the effect of different types of impact loading under normal and artificial gravity conditions on serum concentrations of cartilage oligomeric matrix protein (COMP), a biomarker of cartilage metabolism. Fifteen healthy male adults (26 ± 4 years, 181 ± 4 cm, 77 ± 6 kg) performed four different 30-min impact loading protocols on four experimental days: jumping with artificial gravity elicited by centrifugation in a short-arm centrifuge (AGJ), jumping with artificial gravity generated by low-pressure cylinders in a sledge jump system (SJS), vertical jumping under Earth gravity (EGJ), and running under Earth gravity (RUN). Five blood samples per protocol were taken: 30 min before, immediately before, immediately after, 30 min after, and 60 min after impact loading. Serum COMP concentrations were analyzed in these samples. During the impact exercises, ground reaction forces were recorded. Peak ground reaction forces were significantly different between the three jumping protocols (p < 0.001), increasing from AGJ (14 N/kg) to SJS (22 N/kg) to EGJ (29 N/kg) but were similar in RUN (22 N/kg) compared to SJS. The serum COMP concentration was increased (p < 0.001) immediately after all loading protocols, and then decreased (p < 0.001) at 30 min post-exercise compared to immediately after the exercise. Jumping and running under Earth gravity (EGJ and RUN) resulted in a significantly higher (p < 0.05) increase of serum COMP levels 30 min after impact loading compared to the impact loading under artificial gravity (RUN +30%, EGJ +20%, AGJ +17%, and SJS +13% compared to baseline). In conclusion, both the amplitude and the number of the impacts contribute to inducing higher COMP responses and are therefore likely important factors affecting cartilage metabolism. RUN had the largest effect on serum COMP concentration, presumably due to the high number of impacts, which was 10 times higher than for the jump modalities. Future studies should aim at establishing a dose-response relationship for different types of exercise using comparable amounts of impacts.
CRIS-Team Scopus Importer:2020-09-25
Keywords: articular cartilage; artificial gravity; cartilage oligomeric matrix protein; centrifuge; countermeasure; impact loading; reactive jumping

Similar Impact of Psoriatic Arthritis and Rheumatoid Arthritis on Objective and Subjective Parameters of Hand Function - Liphardt, Anna-Maria; Manger, Eva; Liehr, Sonja; Bieniek, Lisa Maria; Kleyer, Arnd; Simon, David; Tascilar, Koray; Sticherling, Michael; Rech, Jürgen; Schett, Georg; Hueber, Axel (ACR Open Rheumatology, 2020)
ObjectiveThe objective of this study was to compare the impact of psoriatic disease (psoriatic arthritis [PsA] and psoriasis) and rheumatoid arthritis (RA) on objective and subjective parameters of hand function.
CRIS-Team WoS Importer:2021-07-16

Similar Impact of Psoriatic Arthritis and Rheumatoid Arthritis on Objective and Subjective Parameters of Hand Function - Liphardt, Anna-Maria; Manger, Eva; Liehr, Sonja; Bieniek, Lisa; Kleyer, Arnd; Simon, David; Tascilar, Koray; Sticherling, Michael; Rech, Jürgen; Schett, Georg; Hueber, Axel (ARTHRITIS & RHEUMATOLOGY, 2020)
CRIS-Team WoS Importer:2021-01-15

SPATIOTEMPORAL DYNAMICS OF BONE LOSS BEFORE AND AFTER THE ONSET OF RHEUMATOID ARTHRITIS - Tascilar, Koray; Simon, David; Liphardt, Anna-Maria; Meinderink, Timo; Bayat, Sara; Rech, Jürgen; Hueber, A.; Krönke, Gerhard; Schett, Georg; Kleyer, Arnd (ANNALS OF THE RHEUMATIC DISEASES, 2021)
CRIS-Team WoS Importer:2021-10-01

SUBJECTIVE ASSESSMENT OF PHYSICAL FUNCTION DOES NOT SUFFICIENTLY EXPLAIN VARIANCE OF MEASURED HAND FUNCTION AND GRIP STRENGTH IN ARTHRITIS PATIENTS AND NON-ARTHRITIS CONTROLS - Liphardt, Anna-Maria; Tascilar, Koray; Coppers, Birte; Manger, Eva; Liehr, Sonja; Bieniek, Lisa Maria; Bayat, Sara; Simon, David; Sticherling, Michael; Rech, Jürgen; Hueber, A.; Schett, Georg; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2022)
CRIS-Team WoS Importer:2022-11-04

The effect of micro-and hypergravity on serum comp levels in healthy adults - Niehoff, A.; Dreiner, M.; Mundermann, A.; Zaucke, F.; Liphardt, Anna-Maria (OSTEOARTHRITIS AND CARTILAGE, 2019)
CRIS-Team WoS Importer:2019-05-21

The search for the ultimate exercise countermeasure to preserve crew health and ensure mission success in long-duration spaceflight - Fernandez-Gonzalo, Rodrigo; Schneider, Stefan; Heer, Martina; Liphardt, Anna-Maria (Experimental Physiology, 2025)
The current understanding of crew health maintenance is founded upon decades of physiological research conducted in terrestrial spaceflight analogues and in low Earth orbit, particularly on the International Space Station. However, as we progress towards the Lunar Gateway and interplanetary missions, it is imperative that the tools employed to maintain crew health are redefined, including the utilisation of exercise countermeasures. The successful implementation of exercise countermeasures for deep space missions must address a number of challenges, including those posed by new environments with elevated levels of cosmic radiation and solar particle events, extended mission durations and constrained space availability. In this Topical Review, the authors address points that are important (and sometimes critical), but often ignored, in order to define future exercise countermeasures for long-duration space missions. Multi-organ countermeasures, countermeasure enjoyment, time-dependent load variability, the relationship between nutrition and the success of exercise countermeasures, and the individual variability in response to a given countermeasure are presented and discussed. The aim of this article is to raise awareness of important aspects that can profoundly influence the efficacy of exercise countermeasures, thereby affecting the health of the crew and the success of the mission during prolonged spaceflight.
CRIS-Team Scopus Importer:2025-02-14
Keywords: deep-space mission; exercise countermeasure; Mars; Moon; spaceflight

Towards optimal control grasping simulations with the full hand - Heinrich, Simon; Phutane, Uday; Coppers, Birte; Liphardt, Anna-Maria; Leyendecker, Sigrid (conference, 9th GACM Colloquium on Computational Mechanics - for Young Scientists from Academia and Industry, 2022)

Tracking of spaceflight-induced bone remodeling reveals a limited time frame for recovery of resorption sites in humans. - Walle, Matthias; Gabel, Leigh; Whittier, Danielle E.; Liphardt, Anna-Maria; Hulme, Paul A.; Heer, Martina; Zwart, Sara R.; Smith, Scott M.; Sibonga, Jean D.; Boyd, Steven K. (Science Advances, 2024)
Mechanical unloading causes bone loss, but it remains unclear whether disuse-induced changes to bone microstructure are permanent or can be recovered upon reloading. We examined bone loss and recovery in 17 astronauts using time-lapsed high-resolution peripheral quantitative computed tomography and biochemical markers to determine whether disuse-induced changes are permanent. During 6 months in microgravity, resorption was threefold higher than formation. Upon return to Earth, targeted bone formation occurred in high mechanical strain areas, with 31.8% of bone formed in the first 6 months after flight at sites resorbed during spaceflight, significantly higher than the 2.7% observed 6 to 12 months after return. Limited bone recovery at resorption sites after 6 months on Earth indicates a restricted window for reactivating bone remodeling factors in humans. Incomplete skeletal recovery may arise from these arrested remodeling sites, representing potential targets for new interventions, thus providing means to counteract this long-term health risk for astronauts.
EVALuna2:596384

Why and How to Include Data in Biomechanical Optimal Control Simulations - Heinrich, Simon; Coppers, Birte; Liphardt, Anna-Maria; Leyendecker, Sigrid (conference, Interdisciplinary Handsymposium 2023, 2023)